Metal composite hydroxide, positive electrode active material for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery using the same

By using metal composite hydroxides of nickel, manganese, tungsten and other elements in the positive electrode active material of lithium-ion secondary batteries and forming a tungsten concentrated layer on its surface, the problem of poor output characteristics and cycle characteristics in the prior art is solved, and efficient and industrially applicable battery performance is achieved.

CN115385395BActive Publication Date: 2025-04-15SUMITOMO METAL MINING CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202211040738.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-03-08
Filing Date
2018-07-03
Publication Date
2025-04-15
Estimated Expiration
2038-07-03

AI Technical Summary

Technical Problem

When the positive electrode active substance of the conventional lithium-ion secondary battery improves the output characteristics, there are problems such as battery capacity and cycle characteristics that deteriorate battery characteristics, and it is not suitable for the nanometer-level formation of concentrated compound layers in the industry.

Method used

By adding nickel, manganese, tungsten, optional cobalt and element M to the metal composite hydroxide, the metal composite hydroxide is produced by a two-stage crystallization process, and a tungsten concentrated layer is formed on its surface, as a precursor for the lithium metal composite oxide, and the lithium metal composite oxide is obtained by calcination.

Benefits of technology

It realizes the reduction of reaction resistance at the positive electrode of the secondary battery, improves output characteristics, and maintains high crystallinity, which is suitable for industrial-scale manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115385395B_ABST
    Figure CN115385395B_ABST
Patent Text Reader

Abstract

The present invention provides a positive electrode active material with high output and high crystallinity when constituting a secondary battery, and a composite hydroxide as a precursor thereof. A method for producing a metal composite hydroxide, etc., comprising the following steps: a first crystallization step, supplying a first raw material aqueous solution containing a metal element and an ammonium ion donor to a reaction tank, adjusting the pH of the reaction aqueous solution in the reaction tank, and performing a crystallization reaction to obtain a first metal composite hydroxide particle; and a second crystallization step, supplying a second raw material aqueous solution containing a metal element and containing more tungsten than the first raw material aqueous solution and an ammonium ion donor to the reaction aqueous solution containing the first metal composite hydroxide particle, adjusting the pH of the reaction aqueous solution, and performing a crystallization reaction to form a tungsten concentration layer on the surface of the first metal composite hydroxide particle, and obtaining a second metal composite hydroxide particle.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present application is a divisional application of an application with a filing date of July 3, 2018, an application number of 201880059349.9, and an invention name of “Metal composite hydroxide and method for producing the same, positive electrode active material for non-aqueous electrolyte secondary battery and method for producing the same, and non-aqueous electrolyte secondary battery using the same”. Technical Field

[0002] The present invention relates to a metal composite hydroxide and a method for producing the same, a positive electrode active material for a non-aqueous electrolyte secondary battery and a method for producing the same, and a non-aqueous electrolyte secondary battery using the same. Background Art

[0003] In recent years, with the popularization of portable electronic devices such as mobile phones and notebook personal computers, it is strongly desired to develop a small and lightweight non-aqueous electrolyte secondary battery with high energy density. In addition, as a vehicle driving power source for hybrid electric vehicles, plug-in hybrid electric vehicles, battery-type electric vehicles, etc., it is strongly desired to develop a high-output secondary battery.

[0004] As a secondary battery that meets this requirement, there is a lithium ion secondary battery, which is a type of non-aqueous electrolyte secondary battery. A lithium ion secondary battery is composed of a negative electrode, a positive electrode, an electrolyte, etc., and a material capable of inserting and removing lithium is used as an active material used as the material of the negative electrode and the positive electrode.

[0005] Among lithium-ion secondary batteries, those using layered or spinel lithium metal composite oxides as positive electrode active materials can achieve a voltage of 4V. Therefore, research and development are being actively carried out as batteries with high energy density, and some are also being promoted for practical use.

[0006] As positive electrode active materials for such lithium ion secondary batteries, lithium cobalt composite oxide (LiCoO2) which is relatively easy to synthesize, lithium nickel composite oxide (LiNiO2) which uses nickel which is cheaper than cobalt, and lithium nickel cobalt manganese composite oxide (LiNiO2) have been proposed. 1 / 3 Co 1 / 3 Mn 1 / 3 O2), lithium manganese composite oxide (LiMn2O4), lithium nickel manganese composite oxide (LiNi 0.5 Mn 0.5 O2) and other lithium metal composite oxides.

[0007] However, in order to further improve the output characteristics of lithium-ion secondary batteries, it is generally known that there is a method of increasing the specific surface area of ​​the positive electrode active material. When the specific surface area of ​​the positive electrode active material is increased, the reaction area with the electrolyte can be fully ensured when the positive electrode active material is installed in the secondary battery. Therefore, some technologies for improving the output characteristics by controlling the particle structure of the positive electrode active material are proposed.

[0008] For example, Patent Documents 1 to 3 and 10 propose a method for manufacturing a positive electrode active material using a composite hydroxide obtained by a crystallization process divided into two stages as a precursor. The positive electrode active materials described in these patent documents have a small particle size, a narrow particle size distribution, and a hollow structure or space inside the particles, so they have a high specific surface area and excellent output characteristics. However, for example, as a vehicle driving power source for hybrid vehicles, a positive electrode active material with higher output characteristics is required.

[0009] On the other hand, as a method for realizing a positive electrode active material with lower reaction resistance and higher output characteristics, adding different elements to the lithium metal composite oxide constituting the positive electrode active material is being studied. As such different elements, transition metals such as Mo, Nb, W, and Ta that can take high valence numbers are proposed.

[0010] For example, Patent Document 4 describes a lithium transition metal compound powder, which has a lithium transition metal compound having the function of embedding and de-embedding lithium ions as the main component, and in the main component raw material, at least one or more additives that inhibit grain growth and sintering during calcination are added at a ratio of 0.01 mol% or more and less than 2 mol% relative to the total molar amount of transition metal elements in the main component raw material, and then calcined to obtain. In addition, it is recorded that the above-mentioned additive is an oxide containing at least one or more elements selected from Mo, W, Nb, Ta and Re, and the total atomic ratio of the added elements relative to the surface portion of the primary particle and the total atomic ratio of the metal elements other than the aforementioned added elements is more than 5 times the atomic ratio of the entire particle.

[0011] In addition, Patent Document 5 proposes a manufacturing method, which comprises the following steps: adding an alkaline aqueous solution in which a tungsten compound is dissolved in a specific proportion to a lithium metal composite oxide powder and mixing the mixture, thereby dispersing W on the surface of the primary particles of the powder; and heat-treating the mixed alkaline aqueous solution in which the tungsten compound is dissolved and the lithium metal composite oxide powder at a temperature in the range of 100 to 800° C., thereby forming microparticles of lithium tungstate represented by any one of Li2WO4, Li4WO5, and Li6W2O9 on the surface of the lithium metal composite oxide powder or the surface of the primary particles of the powder.

[0012] In addition, Patent Document 6 proposes a positive electrode active material comprising a lithium metal composite oxide, which comprises primary particles and secondary particles formed by aggregation of primary particles, wherein the secondary particles have voids that can be impregnated with an electrolyte near and inside the surface of the secondary particles, and a compound layer having a thickness of less than 20 nm and concentrated with tungsten and containing lithium on the surface or grain boundary of the lithium metal composite oxide. In addition, as a preferred method for obtaining the powder, it is described that a lithium metal composite oxide can be obtained by mixing and roasting a tungsten compound together when mixing a composite hydroxide or a composite oxide with a lithium compound. In addition, in this method, the particle size of the tungsten compound is preferably set to less than 1 / 5 times the average particle size of the composite hydroxide (manganese composite hydroxide) or the composite oxide (manganese composite oxide).

[0013] In addition, Patent Document 7 proposes a method for producing a transition metal composite hydroxide and a positive electrode active material using the hydroxide as a precursor, wherein the method comprises: a process for producing composite hydroxide particles by separating the nucleation process and the particle growth stage by controlling the pH in the crystallization reaction; and a covering process for forming a covering containing tungsten on the surface of the obtained composite hydroxide particles.

[0014] In addition, Patent Document 8 discloses a positive electrode for a lithium ion secondary battery, wherein a positive electrode has a Li x1 Ni a1 Mn b1 Co c1 O2 (wherein, 0.2≤x1≤1.2, 0.6≤a1≤0.9, 0≤b1≤0.3, 0.05≤c1≤0.3, a1+b1+c1=1.0) represented by a first positive electrode active material layer, on the surface of the first positive electrode active material there is a Li x2 Ni a2 Mn b2 Co c2 M d A layer of a second positive electrode active material represented by O2 (wherein M is Mo, W or Nb, 0.2≤x2≤1.2, 0.7≤a2≤0.9, 0≤b2≤0.3, 0.05≤c2≤0.3, 0.02≤d≤0.06, a2+b2+c2+d=1.0).

[0015] In addition, Patent Document 9 discloses a method for producing a nickel-cobalt composite hydroxide, which comprises: a first crystallization step, in which a solution containing nickel, cobalt and manganese, a complex ion forming agent, and an alkaline solution are respectively and simultaneously supplied to a reaction vessel to obtain a nickel-cobalt composite hydroxide; and a second crystallization step, in which, after the first crystallization step, a solution containing nickel, cobalt and manganese, a complex ion forming agent, an alkaline solution, and a solution containing element M are further respectively and simultaneously supplied to obtain a nickel-cobalt composite hydroxide particle. Crystallization of composite hydroxide particles of at least one element selected from the group consisting of Mg, Ca, Ti, Zr, Nb, Ta, Cr, Mo, W, Fe, Cu, Si, Sn, Bi, Ga, Y, Sm, Er, Ce, Nd, La, Cd and Lu, wherein, when the total molar number of nickel, cobalt and manganese supplied in the aforementioned first crystallization step is set to MOL(1) and the total molar number of nickel, cobalt and manganese supplied in the aforementioned second crystallization step is set to MOL(2), 0.30≤MOL(1) / {MOL(1)+MOL(2)}<0.95.

[0016] Prior art literature

[0017] Patent Literature

[0018] Patent Document 1: Japanese Patent Application Publication No. 2012-246199

[0019] Patent Document 2: Japanese Patent Application Publication No. 2013-147416

[0020] Patent Document 3: Japanese Patent Application Publication No. 2016-094307

[0021] Patent Document 4: Japanese Patent Application Publication No. 2008-305777

[0022] Patent Document 5: Japanese Patent Application Publication No. 2013-125732

[0023] Patent Document 6: Japanese Patent Application Publication No. 2014-197556

[0024] Patent Document 7: Japanese Patent Application Publication No. 2012-252844

[0025] Patent Document 8: Japanese Patent Application Publication No. 2012-079608

[0026] Patent Document 9: Japanese Patent Application Publication No. 2016-210674

[0027] Patent Document 10: International Publication No. 2012 / 131881 Summary of the invention

[0028] Problem that the invention aims to solve

[0029] However, in the method described in Patent Document 4, a part of the added elements such as Mo, Ta, and W are substituted for layered Ni in the crystal, which causes a problem in that battery characteristics such as battery capacity and cycle characteristics deteriorate.

[0030] Furthermore, although the output characteristics of the lithium metal composite oxide prepared by the production method described in Patent Document 5 are improved, the cycle characteristics may be insufficient if the thickness of the tungsten fine particles formed on the particle surface is non-uniform.

[0031] In addition, the method described in Patent Document 6 requires that the tungsten compound be crushed once in order to obtain a nanometer-scale tungsten compound, so it is not suitable for industry and is not easy to handle. In addition, the particle size of the obtained particles is uneven, resulting in a deviation in the thickness of the compound layer, so the reduction of the reaction resistance is insufficient, and the effect of improving the output characteristics is limited. In addition, although it is also recorded that tungsten is contained as an additive element in the composite hydroxide (manganese composite hydroxide) in order to obtain the powder, it is difficult for this method to form a compound layer concentrated with tungsten at the nanometer level.

[0032] In addition, the method described in Patent Document 7 adds a process of covering tungsten, so the number of steps increases, which is not preferred in industry. In addition, tungsten is precipitated by controlling pH in the covering process, but the thickness of the covering layer is uneven due to the change of the controlled pH, so it is difficult to cover evenly. In addition, when using a composite oxide obtained by mixing a composite hydroxide unevenly covered with tungsten with lithium, there is a problem that the covering layer of tungsten becomes a resistor, and the output is reduced instead.

[0033] In addition, for the positive electrode active material formed by the method described in Patent Document 8, since the first positive electrode active material and the second positive electrode active material are in different phases, when used in a secondary battery, there are problems such as deviation in structural changes during charge and discharge reactions, cracks occurring during repeated charge and discharge, and deterioration in cycle characteristics.

[0034] In addition, for the composite hydroxide and positive electrode active material obtained by the method described in Patent Document 9, it is recorded that there is a peak of element M (such as tungsten) based on SEM-EDX spectrum in the second layer which exists at a ratio of greater than 5% and less than 50% of the depth in the radial direction. In the positive electrode active material, element M including tungsten is contained closer to the inside than the surface layer of the secondary particles, so the crystallinity is reduced, and there is a possibility that the battery characteristics are reduced when used in a secondary battery.

[0035] In view of these problems, the present invention aims to provide a positive electrode active material having reduced reaction resistance, higher output and high crystallinity when used in a positive electrode of a secondary battery, a metal composite hydroxide as a precursor thereof, and a method for producing the same.

[0036] Solutions for solving problems

[0037] In a first embodiment of the present invention, a method for producing a metal composite hydroxide is provided, wherein the metal composite hydroxide comprises nickel, manganese and tungsten, and optionally cobalt and an element M, and the atomic ratio of each metal element is represented by Ni:Mn:Co:W:M=x:y:z:a:b (x+y+z=1, 0.3≤x≤0.95, 0.05≤y≤0.55, 0≤z≤0.4, 0<a≤0.1, 0≤b≤0.1, and M is one or more elements selected from Mg, Ca, Al, Ti, V, Cr, Zr, Nb, Mo, Hf and Ta), and the method comprises the following steps: a first analysis A crystallization step is to supply a first raw material aqueous solution containing at least one of the metal elements and an ammonium ion donor to a reaction tank, adjust the pH of the reaction aqueous solution in the reaction tank, and perform a crystallization reaction to obtain first metal composite hydroxide particles; and a second crystallization step is to supply a second raw material aqueous solution containing at least one of the metal elements and containing more tungsten than the first raw material aqueous solution and an ammonium ion donor to the reaction aqueous solution containing the first metal composite hydroxide particles, adjust the pH of the reaction aqueous solution, and perform a crystallization reaction to form a tungsten concentration layer on the surface of the first metal composite hydroxide particles to obtain second metal composite hydroxide particles.

[0038] In addition, preferably, the first crystallization step comprises: a nucleation step for performing nucleation, and a particle growth step for performing particle growth; the second crystallization step comprises: a step of performing particle growth following the particle growth step in the first crystallization step; the particle growth in the first crystallization step and the second crystallization step comprises: a step of adjusting the pH of the reaction aqueous solution to be lower than the pH value of the reaction aqueous solution in the nucleation step, and a step of performing the growth in a non-oxidizing atmosphere having an oxygen concentration of 1% by volume or less. In addition, the nucleation in the first crystallization step is preferably performed in an oxidizing atmosphere having an oxygen concentration exceeding 1% by volume.

[0039] In addition, it is preferred that the metal element in the first raw material aqueous solution is supplied to the reaction tank in a range of 50% by mass or more and 95% by mass or less relative to the total amount of metal added in the first crystallization step and the second crystallization step, and then the second raw material aqueous solution in the second crystallization step is supplied. In addition, the second crystallization step preferably includes: a step of forming a tungsten concentration layer from the surface of the second metal composite hydroxide particle in a direction toward the center so that the thickness becomes 100nm or less. In addition, the addition of the second raw material aqueous solution in the second crystallization step is preferably carried out at a time of more than 50% and less than 95% relative to the total time for particle growth in the first crystallization step and the second crystallization step. In addition, the supply of the second raw material aqueous solution is preferably carried out by supplying the first raw material aqueous solution and the tungsten-containing aqueous solution to the reaction aqueous solution respectively. In addition, the tungsten concentration in the tungsten-containing aqueous solution is preferably 0.1 mol / L or more.

[0040] In the second embodiment of the present invention, a metal composite hydroxide is provided, which contains nickel, manganese and tungsten, and optionally cobalt and element M, and the atomic number ratio of each metal element is represented by Ni:Mn:Co:W:M=x:y:z:a:b (x+y+z=1, 0.3≤x≤0.95, 0.05≤y≤0.55, 0≤z≤0.4, 0<a≤0.1, 0≤b≤0.1, M is one or more elements selected from Mg, Ca, Al, Ti, V, Cr, Zr, Nb, Mo, Hf and Ta), and the metal composite hydroxide has a tungsten concentration layer on the surface.

[0041] In addition, the thickness of the tungsten concentration layer is preferably less than 100 nm. In addition, the average particle size is preferably greater than 4.0 μm and less than 9.0 μm, and the index representing the width of the particle size distribution, namely [(d90-d10) / average particle size] is less than 0.65. In addition, it is preferred that the secondary particles are formed by agglomerating a plurality of primary particles, at least a portion of the secondary particles has a hollow structure, and the tap density is 1.2 g / cm 3 Above and 1.9g / cm 3 the following.

[0042] In the third embodiment of the present invention, a method for manufacturing a positive electrode active material for a non-aqueous electrolyte secondary battery is provided, which comprises the following steps: a step of mixing at least one of a metal composite hydroxide obtained by the above-mentioned manufacturing method and a metal composite oxide obtained by heat treating the metal composite hydroxide with a lithium compound to obtain a lithium mixture; and a step of calcining the lithium mixture to obtain a lithium metal composite oxide.

[0043] In the method for producing the positive electrode active material, it is preferred that the value of (d50 of the positive electrode active material / d50 of the metal composite hydroxide), which is an index indicating the degree of aggregation of the lithium metal composite oxide particles, be adjusted to 0.95 or more and 1.05 or less.

[0044] In a fourth embodiment of the present invention, a positive electrode active material for a non-aqueous electrolyte secondary battery is provided, which contains a lithium metal composite oxide, wherein the lithium metal composite oxide contains lithium, nickel, manganese and tungsten and optionally cobalt and an element M, wherein the atomic ratio of each metal element is represented by Li:Ni:Co:Mn:W:M=1+u:x:y:z:a:b (x+y+z=1, -0.05≤u≤0.50, 0.3≤x≤0.95, 0.05≤y≤0.55, 0≤z≤0.4, 0<a≤0.1, 0≤b≤0.1, and M is one or more elements selected from Mg, Ca, Al, Ti, V, Cr, Zr, Nb, Mo, Hf and Ta), and has a tap density of 1.2 g / cm 3 Above 1.99g / cm 3 In the hollow structure below, the lithium metal composite oxide includes secondary particles formed by agglomeration of a plurality of primary particles, and the compound containing tungsten and lithium is concentratedly present in the surface layer of the primary particles existing on the surface or inside of the secondary particles and in the grain boundaries between the primary particles.

[0045] In addition, the positive electrode active material preferably has a crystallite diameter of 120 nm or more on the (003) plane as measured by powder X-ray diffraction.

[0046] In a fifth embodiment of the present invention, there is provided a nonaqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, a separator, and a nonaqueous electrolyte, wherein the positive electrode active material for a nonaqueous electrolyte secondary battery is used as a positive electrode material of the positive electrode.

[0047] Effects of the Invention

[0048] According to the present invention, a positive electrode active material having a reduced reaction resistance, high output and high crystallinity when used for the positive electrode of a secondary battery, and a metal composite hydroxide as a precursor thereof can be provided. In addition, according to the present invention, a secondary battery comprising such a positive electrode active material can be provided. And, according to the present invention, a method for easily manufacturing such a positive electrode active material and a metal composite hydroxide on an industrial scale can be provided. Therefore, the industrial significance of the present invention is great. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 (A) Figure 1 (B) is a schematic diagram showing an example of a metal composite hydroxide.

[0050] Figure 2 This is a diagram showing an example of a method for producing a metal composite hydroxide.

[0051] Figure 3 This is a diagram showing an example of a method for producing a metal composite hydroxide.

[0052] Figure 4 (A) and Figure 4 (B) is a diagram for explaining the timing of starting to add the tungsten-containing aqueous solution.

[0053] Figure 5 (A)~ Figure 5 (D) is a schematic diagram showing an example of a lithium metal composite oxide.

[0054] Figure 6 This is a diagram showing an example of a method for producing a lithium metal composite oxide.

[0055] Figure 7 This is a schematic diagram showing a button-type battery for evaluation used in Examples.

[0056] Figure 8 (A) is a photograph in lieu of a drawing showing W distribution based on surface analysis using EDX of the metal composite hydroxide obtained in Example 4 (upper figure). Figure 8 (B) is an explanatory diagram (lower diagram) illustrating a tungsten concentration layer in a photograph in lieu of a drawing.

[0057] Fig. 9 This is an example of an SEM image showing a cross section of a metal composite hydroxide obtained in an example.

[0058] Fig.10 This is a photograph in lieu of a drawing showing W distribution of the lithium metal composite oxide obtained in Example 4 based on surface analysis using EDX. DETAILED DESCRIPTION

[0059] Hereinafter, with reference to the accompanying drawings, the metal composite hydroxide and its manufacturing method, the positive electrode active material for nonaqueous electrolyte secondary battery and its manufacturing method, and the nonaqueous electrolyte secondary battery of the embodiment are described. It should be noted that the present invention is not limited to the embodiment described below. In addition, in the accompanying drawings, in order to facilitate the understanding of each structure, a part is emphasized or a part is simplified to represent, and the actual structure or shape, scale, etc. are sometimes different.

[0060] 1. Metal composite hydroxide

[0061] Figure 1 (A) and Figure 1 (B) is a schematic diagram showing an example of the metal composite hydroxide of this embodiment. Figure 1As shown in (A), the metal composite hydroxide 10 includes secondary particles 2 formed by agglomerating a plurality of primary particles 1. The shape of the primary particles 1 constituting the secondary particles 2 is not particularly limited, and may be, for example, plate-shaped, needle-shaped, or other fine primary particles smaller than these. It should be noted that the metal composite hydroxide 10 may also include a small amount of individual primary particles 1. Figure 1 (A) and Figure 1 (B) The metal composite hydroxide 10 will be described in detail.

[0062] (Tungsten Concentration Layer)

[0063] like Figure 1 As shown in (B), the metal composite hydroxide 10 (secondary particle 2) has a tungsten concentrated layer 3 formed by tungsten concentration on its surface. The tungsten concentrated layer 3 is formed on the surface (surface layer) of the metal composite hydroxide 10, and refers to a layered region where tungsten is more concentrated than inside the particle. When the metal composite hydroxide 10 having the tungsten concentrated layer 3 is used as a precursor, a positive electrode active material with high crystallinity, reduced reaction resistance, and high output can be obtained. For example, Figure 8 (A) and Figure 8 As shown in (B), the tungsten concentrated layer 3 can be confirmed by detecting the W distribution by surface analysis using an energy dispersive X-ray analyzer (EDX). Figure 1 In (B), the primary particles 1 are not shown.

[0064] As will be described later, the tungsten concentration layer 3 is formed on the lithium metal composite oxide 20 (see Figure 5 ) to form a compound 23 containing tungsten and lithium (e.g., lithium tungstate). The compound 23 containing tungsten and lithium is obtained by mixing a metal composite hydroxide 10 (precursor) with a lithium compound and calcining the mixture to obtain a lithium metal composite oxide 20 (see Figure 5 ) is formed in the process (refer to Figure 6 ).

[0065] For example, Figure 5 (A) and Figure 5 As shown in (B), in the lithium metal composite oxide 20 (positive electrode active material), the compound 23 containing tungsten and lithium is formed on the surface of the primary particles 21 or the grain boundaries between the primary particles 21. Since the ion conductivity of the compound 23 containing tungsten and lithium is high, when the lithium metal composite oxide 20 (positive electrode active material) is used for the positive electrode of a secondary battery, since the compound 23 containing tungsten and lithium is present on the surface of the primary particles 21 in contact with the electrolyte or the grain boundaries between the primary particles 21, the reaction resistance of the positive electrode active material can be reduced, which greatly contributes to the output improvement.

[0066] It should be noted that when using the conventional method for manufacturing a tungsten-containing metal composite hydroxide, the tungsten contained in the metal composite hydroxide (precursor) sometimes inhibits sintering during calcination. Therefore, for the conventional tungsten-containing precursor, although the tungsten in the obtained positive electrode active material helps to reduce the reaction resistance, there is a contradictory problem that the crystallinity of the lithium metal composite oxide constituting the positive electrode active material is reduced, and it is difficult to achieve a lithium metal composite oxide with excellent output characteristics and high crystallinity. However, the metal composite hydroxide 10 of the present embodiment forms a tungsten concentration layer 3 on the surface, so that the effect of inhibiting tungsten sintering is almost not produced during calcination, which can reduce the reaction resistance and improve the crystallinity of the obtained lithium metal composite oxide 20.

[0067] The thickness of the tungsten concentration layer 3 can be set to, for example, 200 nm or less, preferably 100 nm or less, more preferably 10 nm or more and 100 nm or less, and further preferably 20 nm or more and 50 nm or less, from the surface of the metal composite hydroxide 10 in the direction toward the center portion C. When the thickness of the tungsten concentration layer 3 is 100 nm or less, the crystallinity of the lithium metal composite oxide 20 can be further improved, and when the lithium metal composite oxide 20 is used for the positive electrode of a secondary battery, the reaction resistance can be further reduced and the output characteristics can be improved.

[0068] It should be noted that the thickness of the tungsten concentrated layer 3 can be measured as follows: the metal composite hydroxide 10 is embedded in a resin or the like and cut, a sample of the cross section of the secondary particle 2 is prepared, and a surface analysis of the W distribution using EDX is performed. Specifically, in the sample of the cross section of the secondary particle 2, 20 cross sections of the secondary particles 2 that reach 80% or more of the volume average particle size (MV) measured using a laser diffraction scattering particle size analyzer are randomly selected, and in each selected cross section of the secondary particle 2, the thickness (width) of 5 or more locations (tungsten concentrated layer 3) where W is detected as concentrated is measured from the surface of the metal composite hydroxide 10 in the direction toward the center C, and the average value of the thickness of the tungsten concentrated layer 3 in each secondary particle 2 is obtained. Then, the average value of the thickness of each of the 20 selected secondary particles 2 is calculated, so that the thickness of the tungsten concentrated layer 3 can be obtained.

[0069] It should be noted that when the thickness of the tungsten concentration layer 3 exceeds 100 nm, the sintering inhibition effect of tungsten becomes greater during calcination, which sometimes hinders the growth of primary particles. Therefore, in the obtained lithium metal composite oxide 20, a large number of primary particles 21 with a small crystallite diameter are formed, resulting in a large number of grain boundaries, so the reaction resistance in the positive electrode is sometimes increased. In addition, as the growth of the primary particles 21 is suppressed, the crystallinity of the lithium metal composite oxide 20 is sometimes reduced.

[0070] On the other hand, when the thickness of the tungsten concentration layer 3 is less than 10 nm, the specific surface area becomes large, and the metal composite hydroxides 10 are easily aggregated during calcination, so the packing density of the obtained lithium metal composite oxide 20 (positive electrode active material) is sometimes reduced, and the battery capacity per unit volume is reduced. In addition, sometimes the compound 23 containing tungsten and lithium cannot be fully formed in the lithium metal composite oxide 20, and the lithium ion conductivity is insufficient.

[0071] In addition, the thickness of the tungsten concentration layer 3 can be set to 3% or less, for example, from the surface of the secondary particle 2 in the direction toward the center C of the secondary particle 2 relative to the average particle size of the metal composite hydroxide 10. In addition, from the viewpoint of further improving the crystallinity of the lithium metal composite oxide 20 and further reducing the reaction resistance, the thickness of the tungsten concentration layer 3 is preferably 2% or less, more preferably 0.1% or more and 2% or less, more preferably 0.1% or more and 1% or less, and further preferably 0.1% or more and 0.5% or less. It should be noted that the average particle size of the metal composite hydroxide 10 refers to the volume average particle size (MV).

[0072] (Average particle size)

[0073] The average particle size of the metal composite hydroxide 10 is not particularly limited, but is preferably 4.0 μm or more, more preferably 4.0 μm or more and 9.0 μm or less, and further preferably 4.0 μm or more and 7 μm or less. The average particle size of the metal composite hydroxide 10 is related to the average particle size of the lithium metal composite oxide 20 (positive electrode active material) using the metal composite hydroxide 10 as a precursor. Therefore, by controlling the average particle size of the metal composite hydroxide 10 within the above range, the lithium metal composite oxide 20 (see Figure 5 ) can also be controlled within the above range.

[0074] When the average particle size of the metal composite hydroxide 10 is less than 4.0 μm, the specific surface area becomes large, and the calcination step (step S40, see Figure 6 ), sometimes the particles of the metal composite hydroxide 10 are easily aggregated with each other, the packing density of the obtained positive electrode active material is reduced, and the battery capacity per unit volume is reduced. It should be noted that in this specification, the average particle size of the metal composite hydroxide 10 refers to the volume average particle size (MV), which can be obtained based on the volume cumulative value measured by a laser diffraction scattering particle size analyzer, for example.

[0075] (Particle size distribution)

[0076] For the metal composite hydroxide 10, the index representing the width of the particle size distribution, namely [(d90-d10) / average particle size] is less than 0.65. The particle size distribution of the lithium metal composite oxide 20 (positive electrode active material) is greatly affected by the metal composite hydroxide 10 as its precursor. Therefore, when a metal composite hydroxide 10 containing a large amount of fine particles or coarse particles is used as a precursor, a large amount of fine particles or coarse particles will also be contained in the lithium metal composite oxide 20. A secondary battery using such a lithium metal composite oxide 20 as a positive electrode active material sometimes has reduced battery characteristics such as thermal stability, cycle characteristics, and output characteristics. Therefore, when the [(d90-d10) / average particle size] of the metal composite hydroxide 10 is adjusted to the above range, the particle size distribution of the lithium metal composite oxide 20 obtained using it as a precursor can be narrowed, and the mixing of fine particles or coarse particles can be suppressed.

[0077] In addition, the lower limit of [(d90-d10) / average particle size] of the metal composite hydroxide 10 is not particularly limited, but is preferably set to about 0.25 or more from the viewpoint of cost and productivity. In the case of industrial-scale production, it is unrealistic to use a metal composite hydroxide 10 with too small [(d90-d10) / average particle size].

[0078] It should be noted that d10 refers to the particle size when the cumulative volume of particles of each particle size accumulated from the side with the smaller particle size reaches 10% of the total volume of all particles, and d90 refers to the particle size when the cumulative volume of particles accumulated from the side with the smaller particle size reaches 90% of the total volume of all particles. In addition, similarly to the average particle size, d10 and d90 can be obtained based on the volume cumulative value measured by a laser diffraction scattering particle size analyzer.

[0079] (Particle structure)

[0080] The particle structure of the secondary particle 2 is not particularly limited, and may have a solid structure with almost no voids inside the particle, a hollow structure with a hollow portion in the center of the particle, a void structure with multiple voids inside the particle, a multilayer structure with layered voids inside the particle, and other conventionally known particle structures. It should be noted that the particle structure of the secondary particle 2 (metal composite hydroxide 10) is maintained in the particle structure of the secondary particle 22 of the lithium metal composite oxide 20 described later. For example, in the case where the secondary particle 2 has a hollow structure (see Fig. 9 ), the secondary particles 22 of the obtained lithium metal composite oxide 20 also have a hollow structure, the contact area with the electrolyte is increased, and the output characteristics are further improved in cooperation with the effect of the above-mentioned tungsten concentration layer 3. Therefore, from the viewpoint of further improving the output characteristics, the secondary particles 2 preferably have a hollow structure.

[0081] (Tap density)

[0082] The tap density of the metal composite hydroxide 10 is not particularly limited, but is preferably 1.2 g / cm 3 Above and 1.9g / cm 3 Below, more preferably 1.3 g / cm 3 Above and 1.7g / cm 3 The tap density of the metal composite hydroxide 10 is related to the tap density of the lithium metal composite oxide 20 (positive electrode active material) using the metal composite hydroxide 10 as a precursor. Therefore, by controlling the tap density of the metal composite hydroxide 10 within the above range, the lithium metal composite oxide 20 (see Figure 5 ) can also be controlled within the above range. When the lithium metal composite oxide 20 is used as a positive electrode, a secondary battery with a high battery capacity can be obtained. On the other hand, when the tap density of the metal composite hydroxide 10 is less than 1.2 g / cm 3 In the case of, for example, in the calcination step (step S40, see Figure 6 ), sometimes the stacking height becomes high when stacked in the sagger, and the calcination is insufficient, thereby reducing the crystallinity.

[0083] (composition)

[0084] The composition of the metal composite hydroxide 10 is not particularly limited. For example, the metal composite hydroxide 10 preferably contains Ni, Co and W, and optionally Mn and M, and the atomic ratio (A) of each metal element is Ni:Co:Mn:W:M=x:y:z:a:b (x+y+z=1, 0.3≤x≤0.95, 0.05≤y≤0.55, 0≤z≤0.4, 0<a≤0.1, 0≤b≤0.1, and M is one or more elements selected from Mg, Ca, Al, Ti, V, Cr, Zr, Nb, Mo, Hf and Ta).

[0085] It should be noted that, since the ratio (A) of the number of atoms of each metal element in the metal composite hydroxide 10 is also maintained in the lithium metal composite oxide 20, the preferred range of the composition of nickel, manganese, cobalt, tungsten, and element M constituting the metal composite hydroxide 10 in the metal composite hydroxide 10 represented by the above-mentioned element ratio (A) and its meaning are the same as those of the positive electrode active material represented by the ratio (B) described later. Therefore, the description of these matters is omitted here.

[0086] Alternatively, the metal composite hydroxide 10 may be represented by the general formula (A1): Ni x Mn yCo z W a M b (OH) 2+α (x+y+z=1, 0.3≤x≤0.95, 0.05≤y≤0.55, 0≤z≤0.4, 0<a≤0.1, 0≤b≤0.1, 0≤α≤0.5, M is one or more elements selected from Mg, Ca, Al, Ti, V, Cr, Zr, Nb, Mo, Hf and Ta).

[0087] In the above general formula (A1), from the viewpoint of further improving the capacity characteristics of a secondary battery using the obtained positive electrode active material, the composition is preferably set to general formula (A2): Ni x Mn y Co z W a M b (OH) 2+α (x+y+z=1, 0.7<x≤0.95, 0.05≤y≤0.1, 0≤z≤0.2, 0<a≤0.1, 0≤b≤0.1, 0≤α≤0.5, M is one or more elements selected from Mg, Ca, Al, Ti, V, Cr, Zr, Nb and Mo.) Furthermore, from the viewpoint of balancing thermal stability and battery capacity, in the general formula (A2), the value of x is more preferably set to 0.7<x≤0.9, and further preferably set to 0.7<x≤0.85.

[0088] In the above general formula (A1), from the viewpoint of further improving the thermal stability of a secondary battery using the obtained positive electrode active material, the composition is preferably set to general formula (A3): Ni x Mn y Co z W a M b (OH) 2+α (x+y+z=1, 0.3≤x≤0.7, 0.1≤y≤0.55, 0≤z≤0.4, 0<a≤0.1, 0≤b≤0.1, 0≤α≤0.5, M is one or more elements selected from Al, Ti, V, Cr, Zr, Nb, Mo, Hf and Ta).

[0089] 2. Method for producing metal composite hydroxide

[0090] Figure 2-Figure 3: is a diagram showing an example of a method for producing a metal composite hydroxide according to the present embodiment. The method for producing the present embodiment is a method for producing a metal composite hydroxide comprising nickel, manganese and tungsten and optionally cobalt and element M, and wherein the atomic ratio of each metal element is represented by Ni:Mn:Co:W:M=x:y:z:a:b (x+y+z=1, 0.3≤x≤0.95, 0.05≤y≤0.55, 0≤z≤0.4, 0<a≤0.1, 0≤b≤0.1, M is one or more elements selected from Mg, Ca, Al, Ti, V, Cr, Zr, Nb, Mo, Hf and Ta) by a crystallization reaction. By the method for producing the present embodiment, a metal composite hydroxide 10 having the above-mentioned characteristics can be easily produced on an industrial scale.

[0091] [Crystallization reaction]

[0092] like Figure 2 As shown, the manufacturing method of the metal composite hydroxide 10 comprises the following steps: a first crystallization step (step S10), in which a first raw material aqueous solution containing, for example, nickel (Ni) and manganese (Mn) and optionally cobalt (Co) and / or a metal element (M), and an ammonium ion donor are supplied into a reaction tank to carry out a crystallization reaction to obtain first metal composite hydroxide particles; and a second crystallization step (step S20), in which a second raw material aqueous solution containing more tungsten than the first raw material aqueous solution and an ammonium ion donor are supplied into a reaction aqueous solution containing the above-mentioned first metal composite hydroxide particles to carry out a crystallization reaction to form a tungsten concentration layer on the surface of the first metal composite hydroxide particles, thereby obtaining second metal composite hydroxide particles.

[0093] In the method for producing the metal composite hydroxide 10, in the second crystallization step (step S20), a tungsten concentration layer 3 is formed on the surface of the first composite hydroxide particles obtained by the first crystallization step (step S10), thereby obtaining the second metal composite hydroxide particles. The interior of the second metal composite hydroxide particles is composed of the first metal composite hydroxide particles that do not contain tungsten or have a low tungsten content. Therefore, the crystallinity of the particles of the lithium metal composite oxide 20 (positive electrode active material) obtained using the first metal composite hydroxide particles as a precursor is high, and the compound 23 containing tungsten and lithium derived from the tungsten concentration layer 3 is present on the surface of the primary particles or the grain boundaries between the primary particles. In addition, the output characteristics of the secondary battery using the lithium metal composite oxide 20 as the positive electrode are excellent.

[0094] like Figure 3As shown, the first crystallization step (step S10) preferably further includes: a nucleation step (step S11) for mainly performing nucleation, and a particle growth step (step S12) for mainly performing particle growth. By, for example, controlling the pH of the reaction aqueous solution, the nucleation step (step S11) and the particle growth step (step S12) can be clearly separated, and a metal composite hydroxide 10 having a narrow particle size distribution and a uniform particle size can be obtained. It should be noted that the second crystallization step (step S20) is a step that follows the particle growth step (step S12) in the first crystallization step (step S10) and mainly performs particle growth.

[0095] It should be noted that the method for manufacturing the nickel composite hydroxide (metal composite hydroxide) comprising the two-stage crystallization process is disclosed in, for example, Patent Documents 2 to 3, Patent Document 10, etc., and the detailed conditions can be appropriately adjusted by referring to these documents. In addition, the method for manufacturing the metal composite hydroxide of the present embodiment can form a tungsten concentration layer 3 having a desired film thickness using the conditions of a known crystallization method as described later, and can therefore be easily applied to industrial-scale production.

[0096] Below, refer to Figure 3 , each step of the production method including the nucleation step (step S11) and the particle growth step (step S12) will be described. It should be noted that the following description is an example of the production method of the metal composite hydroxide 10, and is not limited to this method.

[0097] (1) First Crystallization Step (Step S10)

[0098] (Nucleation process)

[0099] First, the first raw aqueous solution and the ammonium ion donor are supplied, and the pH of the reaction aqueous solution (nucleation aqueous solution) in the reaction tank is controlled within a specified range to perform nucleation (step S11). For the first raw aqueous solution, for example, a compound containing a transition metal as a raw material is dissolved in water to prepare it. It should be noted that in the manufacturing method of the metal composite hydroxide described below, the composition ratio of the metal composite hydroxide formed by crystallization in each process is the same as the composition ratio of each metal in the raw aqueous solution, and therefore, the composition ratio of each metal in each raw aqueous solution can be used as the composition ratio of each metal of the target metal composite hydroxide. In addition, the first raw aqueous solution may contain a small amount of tungsten or may not contain tungsten.

[0100] First, an alkaline aqueous solution and an aqueous solution containing an ammonium ion donor are supplied to a reaction tank and mixed to prepare an aqueous solution before the reaction in which the pH value is 12.0 or more and 14.0 or less based on a liquid temperature of 25°C and the ammonium ion concentration is 3g / L or more and 25g / L or less. The reaction atmosphere in the reaction tank is not particularly limited, and for example, in the case of obtaining a metal composite hydroxide with a hollow structure, it is preferably set to an oxidizing atmosphere. The oxidizing atmosphere preferably has an oxygen concentration exceeding 1% by volume, and the oxygen concentration may exceed 10% by volume, or may be 20% or more by volume, or may be set to an atmospheric atmosphere. For the control of the atmosphere, for example, adjustment is performed by introducing nitrogen and oxygen. It should be noted that the pH value of the aqueous solution before the reaction can be measured with a pH meter, and the ammonium ion concentration can be measured with an ion meter.

[0101] Next, the first raw material aqueous solution is supplied into the reaction tank while stirring the pre-reaction aqueous solution in the reaction tank to form a reaction aqueous solution (aqueous solution for nucleation). It should be noted that in the nucleation process (step S11), the pH value and the concentration of ammonium ions in the aqueous solution for nucleation will change with the nucleation in the reaction aqueous solution. Therefore, it is preferred to supply an alkaline aqueous solution and an ammonia aqueous solution in a timely manner, and control the pH value of the liquid in the reaction tank to be maintained in the range of pH 12.0 to 14.0 based on a liquid temperature of 25°C, and the concentration of ammonium ions to be maintained in the range of 3 g / L to 25 g / L. When the pH value of the reaction aqueous solution (aqueous solution for nucleation) is within the above range, the nucleus hardly grows, and nucleation occurs preferentially.

[0102] The pH value of the reaction aqueous solution (aqueous solution for nucleation) measured based on a liquid temperature of 25°C is preferably 12.0 or more and 14.0 or less, more preferably 12.3 or more and 13.5 or less, and further preferably 12.5 or more and 13.3 or less. When the pH is in the above range, the growth of the nucleus can be suppressed, and nucleation is preferentially performed, so that the nucleus generated in the nucleation process can be homogeneous and have a narrow particle size distribution. On the other hand, when the pH value is lower than 12.0, the growth of the nucleus (particles) and nucleation are performed simultaneously, and therefore, the obtained metal composite hydroxide particles sometimes become uneven in particle size and deteriorate in particle size distribution. In addition, when the pH value exceeds 14.0, the nucleus generated is sometimes too fine, resulting in gelation of the reaction aqueous solution (aqueous solution for nucleation).

[0103] It should be noted that the pH value in the reaction aqueous solution (nucleation aqueous solution) preferably fluctuates within ±0.2. If the pH value fluctuates greatly, the ratio of nucleation amount and particle growth is not constant, and it is difficult to obtain metal composite hydroxide particles with a narrow particle size distribution.

[0104] The ammonium ion concentration of the reaction aqueous solution (nucleation aqueous solution) is preferably adjusted to more than 3g / L and less than 25g / L, more preferably in the scope of more than 5g / L and less than 20g / L.Ammonium ion plays a role as a complexing agent in the reaction aqueous solution, and therefore when ammonium ion concentration is less than 3g / L, the solubility of metal ion cannot be kept constant or the reaction aqueous solution is easily gelled, causing being difficult to obtain the metal composite hydroxide particles of shape, regular particle diameter.On the other hand, when ammonium ion concentration exceeds 25g / L, the solubility of metal ion is too large, and thus the amount of metal ion remaining in the reaction aqueous solution increases, and sometimes becomes the reason of composition deviation etc.

[0105] It should be noted that if the ammonium ion concentration changes during the crystallization reaction, the solubility of the metal ion changes, resulting in the inability to form uniform metal composite hydroxide particles. Therefore, preferably, the fluctuation range of the ammonium ion concentration is controlled within a certain range by a nucleation process (step S11) and a particle growth process (step S12), specifically, preferably controlled within a fluctuation range of ± 5g / L.

[0106] In the nucleation process (step S11), the first raw material aqueous solution, the alkaline aqueous solution, and the aqueous solution containing the ammonium ion donor are supplied to the reaction aqueous solution (aqueous solution for nucleation), so as to continuously generate new nuclei. Then, when a predetermined amount of nuclei are generated in the aqueous solution for nucleation, the nucleation process is terminated. At this time, the amount of nuclei generated can be determined by the amount of the metal compound contained in the raw material aqueous solution supplied to the aqueous solution for nucleation.

[0107] The amount of nuclei generated in the nucleation process (step S11) is not particularly limited, but from the viewpoint of obtaining metal composite hydroxide particles with a narrow particle size distribution, it is preferably set to be greater than 0.1 atomic % and less than 2 atomic %, and more preferably set to be greater than 0.1 atomic % and less than 1.5 atomic %, relative to the metal elements in the metal compounds contained in the raw aqueous solution supplied through the crystallization process (including the first crystallization process and the second crystallization process).

[0108] In addition, in the nucleation process, the upper limit of the temperature of the reaction aqueous solution (nucleation aqueous solution) is not particularly limited, and is preferably 60°C or less, and more preferably 50°C or less. This is because when the temperature of the reaction aqueous solution (nucleation aqueous solution) exceeds 60°C, there is a concern that strain will be generated in the primary crystal and the tap density will begin to decrease. It should be noted that the lower limit of the temperature of the reaction aqueous solution (nucleation aqueous solution) is, for example, 20°C or more.

[0109] The reaction atmosphere in the nucleation step (step S11) is not particularly limited. For example, when the tap density is 1.20 g / cm 3In the case of the metal composite hydroxide having a hollow structure as described above, it is preferably controlled to be an oxidizing atmosphere with an oxygen concentration exceeding 1 volume %, or an atmosphere with an oxygen concentration exceeding 10 volume %, or an atmosphere with an oxygen concentration exceeding 20 volume %, or it can be set to an atmospheric atmosphere.

[0110] (Particle Growth Process)

[0111] Next, particle growth is performed in a reaction aqueous solution (aqueous solution for particle growth) whose pH has been adjusted to a specific range (step S12). The reaction aqueous solution (aqueous solution for particle growth) is formed by supplying a first raw material aqueous solution, an alkaline aqueous solution, and an aqueous solution containing an ammonium ion donor to a reaction aqueous solution containing the generated nuclei. For the reaction aqueous solution (aqueous solution for particle growth), it is preferred to adjust the pH value to be greater than 10.5 and less than 12.0 based on a liquid temperature of 25°C, and the ammonium ion concentration to be greater than 3 g / L and less than 25 g / L. Thus, in the reaction aqueous solution (aqueous solution for particle growth), particle growth takes precedence over nucleation.

[0112] For the reaction atmosphere in the reaction tank, it is preferably set to a non-oxidizing atmosphere, preferably an atmosphere (non-oxidizing atmosphere) with an oxygen concentration of less than 1% by volume. When the oxygen concentration of the reaction atmosphere in the reaction tank is less than 1% by volume, it is possible to suppress unnecessary oxidation, and to grow the nuclei generated in the nucleation process (step S11) to a certain range, so that the crystallinity of the obtained positive electrode active material can be further improved. For the control of the atmosphere, for example, adjustment is made by introducing nitrogen. It should be noted that the switch from an oxidizing atmosphere to a non-oxidizing atmosphere can be performed at the start of the particle growth process (step S12), or it can be switched to a non-oxidizing atmosphere during the particle growth process (step S12).

[0113] Specifically, after the nucleation process is completed, the pH value of the nucleation aqueous solution in the reaction tank is adjusted to 10.5 or more and 12.0 or less based on a liquid temperature of 25°C, to form an aqueous solution for particle growth as a reaction aqueous solution in the particle growth process (step S12). The pH value can be adjusted by stopping only the supply of the alkaline aqueous solution, but from the viewpoint of improving the uniformity of the particle size, it is preferred to temporarily stop the supply of all aqueous solutions and adjust the pH value. In addition, the pH value can also be adjusted by supplying an inorganic acid of the same type as the acid constituting the transition metal-containing compound as a raw material to the reaction aqueous solution (nucleation aqueous solution). For example, when a sulfate of a transition metal is used as a raw material, it can also be performed by supplying sulfuric acid.

[0114] Next, the supply of the first raw material aqueous solution is started again while stirring the reaction aqueous solution (aqueous solution for particle growth). At this time, since the pH value of the aqueous solution for particle growth is within the above range, almost no new nuclei are generated, and nuclear (particle) growth is performed to form the first metal composite hydroxide particles with a specified particle size. It should be noted that in the particle growth step (step S12), as the particles grow, the pH value and ammonium ion concentration of the aqueous solution for particle growth will also change. Therefore, it is necessary to supply an alkaline aqueous solution and an ammonia aqueous solution in a timely manner to maintain the pH value and ammonium ion concentration within the above range.

[0115] The pH value of the reaction aqueous solution (particle growth aqueous solution) is controlled to be in the range of 10.5 to 12.0, preferably 11.0 to 12.0, and more preferably 11.5 to 11.9, based on a liquid temperature of 25°C. When the pH is in the above range, the generation of new nuclei is suppressed, and particle growth is preferentially performed, so that the obtained metal composite hydroxide can be homogeneous and have a narrow particle size distribution. On the other hand, when the pH value is lower than 10.5, the solubility of metal ions increases due to the increase in ammonium ion concentration, so that not only the rate of crystallization reaction slows down, but also the amount of metal ions remaining in the reaction aqueous solution increases, and sometimes productivity deteriorates. In addition, when the pH value exceeds 12.0, sometimes the amount of nucleation in the particle growth process increases, and the particle size of the obtained metal composite hydroxide particles becomes uneven and the particle size distribution deteriorates.

[0116] It should be noted that the pH value in the reaction aqueous solution (particle growth aqueous solution) preferably fluctuates within ±0.2. If the pH value fluctuates greatly, the ratio of nucleation amount and particle growth is not constant, and it is difficult to obtain a metal composite hydroxide with a narrow particle size distribution.

[0117] In addition, the pH value of the particle growth process (step S12) is preferably adjusted to a value lower than the pH value of the nucleation process (step S11). In order to clearly separate nucleation and particle growth, the pH value of the particle growth process (step S12) is preferably lower than the pH value of the nucleation process (step S11) by at least 0.5, and more preferably at least 0.8.

[0118] For example, when the pH value of the reaction aqueous solution (nucleation process and / or particle growth process) is 12.0, since it is the boundary condition between nucleation and particle growth, it can be set as the condition of either the nucleation process or the particle growth process according to whether there is a core in the reaction aqueous solution. That is, when the pH value of the nucleation process is set to 12.0 after a large amount of nucleation is performed, since there are a large number of cores in the reaction aqueous solution, particle growth occurs preferentially, thereby obtaining metal composite hydroxide particles with a narrow particle size distribution. On the other hand, when the pH value of the nucleation process is set to 12.0, since there is no growing core in the reaction aqueous solution, nucleation occurs preferentially, and by making the pH value of the particle growth process less than 12.0, the generated core grows, thereby obtaining good metal composite hydroxide particles.

[0119] The ammonium ion concentration of the reaction aqueous solution (particle growth aqueous solution) can be set to the same preferred range as the ammonium ion concentration in the above-mentioned reaction aqueous solution (nucleation aqueous solution). In addition, the variation range of the ammonium ion concentration can also be set to the same preferred range as the above-mentioned reaction aqueous solution (nucleation aqueous solution).

[0120] (2) Second Crystallization Step

[0121] Next, a second raw material aqueous solution containing a metal element and containing more tungsten than the first raw material aqueous solution and an ammonium ion donor are supplied to the reaction aqueous solution containing the first metal composite hydroxide particles to perform a crystallization reaction (step S20). Thus, second metal composite hydroxide particles having a tungsten concentration layer formed on the surface of the first metal composite hydroxide particles are obtained.

[0122] The particle growth is carried out with the secondary particles formed by the aggregation of a plurality of primary particles as the nucleus, so in the second crystallization step, the second raw material aqueous solution containing more tungsten than the first raw material aqueous solution and the ammonium ion donor can be continuously supplied to the reaction aqueous solution containing the first metal composite hydroxide particles from the particle growth step (step S12) to carry out the second crystallization step (step S20). Thus, a tungsten concentration layer is formed on the peripheral portion of the secondary particles constituting the first composite oxide particles.

[0123] The method for producing a metal composite hydroxide according to the present embodiment can easily control the thickness of the tungsten concentrated layer formed on the periphery of the first metal composite hydroxide particles by, for example, adjusting the timing of starting to add the second raw material aqueous solution (ie, the timing of starting the second crystallization step).

[0124] The second raw material aqueous solution can be supplied to the reaction tank at a time when the metal element in the first raw material aqueous solution is supplied to the reaction tank in a manner of, for example, 10% by mass or more relative to the total amount of metal added in the first crystallization step and the second crystallization step, thereby starting the second crystallization reaction (step S20). Thus, a tungsten concentrated layer can be easily formed on the surface of the first metal composite hydroxide particles.

[0125] In addition, from the viewpoint of obtaining a positive electrode active material with higher crystallinity and further reduced reaction resistance when used for the positive electrode of a secondary battery, the second raw aqueous solution can be supplied to the reaction tank at the moment when the metal elements in the first raw aqueous solution are supplied to the reaction tank in a range preferably from 50 weight % to 95 weight %, and more preferably from 75 weight % to 90 weight %, relative to the total amount of metal added in the first crystallization step and the second crystallization step, to start the second crystallization reaction (step S20).

[0126] The second crystallization step (step S20) is a step for performing particle growth similarly to the particle growth step (step S12), and therefore, the pH, temperature, ammonium ion concentration of the reaction aqueous solution, the reaction atmosphere in the reaction tank, etc. can be set to the same conditions as those in the particle growth step (step S12). By continuously performing the second crystallization step (step S20) under the same conditions as those in the particle growth step (step S12), a tungsten concentration layer can be formed on the surface of the first metal composite hydroxide particles in a simple and productive manner.

[0127] In addition, the supply of the second raw material aqueous solution may be carried out by separately preparing a raw material aqueous solution containing a metal element other than tungsten and an aqueous solution containing tungsten, and supplying them to the reaction tank. By separately supplying an aqueous solution containing tungsten, a tungsten concentrated layer can be formed more simply and uniformly. Figure 3 As shown, the second raw material aqueous solution may also include the first raw material aqueous solution and an aqueous solution containing tungsten (W), and each aqueous solution is supplied to the reaction aqueous solution separately. Thus, by changing the concentration of the aqueous solution containing tungsten and the flow rate when the aqueous solution containing tungsten is supplied to the reaction tank, a tungsten concentrated layer can be uniformly formed, and the thickness of the tungsten concentrated layer can be easily adjusted.

[0128] The tungsten-containing aqueous solution can be prepared, for example, by dissolving a tungsten compound in water. The tungsten compound used is not particularly limited, and a compound containing tungsten but not containing lithium can be used, but sodium tungstate is preferably used.

[0129] The concentration of tungsten (W) in the tungsten-containing aqueous solution is not particularly limited, and may be, for example, 0.1 mol / L or more, preferably 0.1 mol / L or more and 0.5 mol / L or less, and preferably 0.2 mol / L or more and 0.4 mol / L or less. In addition, the addition flow rate of the tungsten-containing aqueous solution is not particularly limited, and may be, for example, 5 L / min or more and 20 L / min or less, and preferably 10 L / min or more and 15 L / min or less.

[0130] The thickness of the tungsten concentrated layer can also be controlled by adjusting the concentration of the tungsten-containing aqueous solution or adjusting the addition flow rate of the aqueous solution. For example, when the concentration and addition flow rate of the tungsten-containing aqueous solution are kept constant, the thickness and concentration of the formed tungsten concentrated layer can be more accurately and easily adjusted by adjusting the time when the tungsten-containing aqueous solution is started to be added.

[0131] Figure 4 (A) and (B) are diagrams showing a preferred example of the manufacturing method of this embodiment. Figure 4 (A) and (B) illustrate the timing of starting to add the tungsten-containing aqueous solution (starting timing of the second crystallization step) in a case where the first crystallization step (step S10) is separately provided with a nucleation step (step S11) and a particle growth step (step S12), and the first raw material aqueous solution and the tungsten-containing aqueous solution are supplied following the above-mentioned particle growth step (step S12) to carry out the second crystallization step (step S20).

[0132] Figure 4 (A) is a diagram showing an example of adding a tungsten-containing aqueous solution from the time when 75% of the total time of particle growth from the start time of particle growth to the end time of particle growth (the end time of the crystallization step) has passed. Figure 4 As shown below (A), a tungsten concentrated layer 3 can be formed on the surface (periphery) of the secondary particles (first metal composite hydroxide particles). It should be noted that when the tungsten-containing aqueous solution is added throughout the entire process from the start to the end of particle growth, the tungsten concentrated layer 3 is not formed.

[0133] Figure 4 (B) is a diagram showing an example of adding a tungsten-containing aqueous solution from the time when 87.5% of the total time of particle growth from the start time of particle growth to the end time of particle growth (end of the crystallization process) has passed. Figure 4 As shown in the lower part of (B), a more concentrated tungsten concentrated layer 3 can be formed on the surface layer (outer periphery) of the secondary particles (first metal composite hydroxide particles) compared to the case where the addition is started from the time when 75% has passed.

[0134] In the case of supplying the first raw aqueous solution and the tungsten-containing aqueous solution to carry out the second crystallization step (step S20) as described above, the supply of the tungsten-containing aqueous solution (the second raw aqueous solution) can be carried out at a time of, for example, more than 10%, preferably more than 50% and less than 95%, and more preferably more than 75% and less than 90%, relative to the total time from the start to the end of the above-mentioned particle growth in the first crystallization step and the second crystallization step. When the time of starting the supply is within the above range, a tungsten concentrated layer can be obtained easily and with good productivity. In addition, within the above range, when the time of starting to add the tungsten-containing aqueous solution is later, there is a tendency to increase the crystallite diameter of the obtained positive electrode active material. It is necessary that the addition of the tungsten-containing aqueous solution continues until the crystallization reaction ends.

[0135] Hereinafter, each raw material and conditions preferably used in the above-mentioned crystallization step will be described.

[0136] (First and second raw material aqueous solutions)

[0137] The first raw material aqueous solution and the second raw material aqueous solution contain nickel and manganese, and optionally cobalt, element M and tungsten. In addition, the first raw material aqueous solution may contain tungsten or may not contain tungsten. In the second crystallization step, when the first raw material aqueous solution and the aqueous solution containing tungsten are used as the second raw material aqueous solution, the ratio of the metal elements in the first raw material aqueous solution is the composition ratio of the metal composite hydroxide finally obtained (excluding tungsten). Therefore, the first raw material aqueous solution can appropriately adjust the content of each metal element according to the composition of the target metal composite hydroxide. For example, in the case of obtaining particles of a metal composite hydroxide represented by the above ratio (A), the ratio of the metal elements in the first raw material aqueous solution and the second raw material aqueous solution can be adjusted to Ni: Mn: Co: M = x: y: z: b (where x + y + z = 1, 0.3 ≤ x ≤ 0.95, 0.05 ≤ y ≤ 0.55, 0 ≤ z ≤ 0.4, 0 ≤ b ≤ 0.1). It should be noted that the first raw material aqueous solution only needs to contain at least one of the elements represented by the above ratio (A). In addition, the compositions of the metal elements in the first raw material aqueous solution and the second raw material aqueous solution used in the first crystallization step and the second crystallization step may be different. In this case, the total content of the metal elements in the first and second raw material aqueous solutions used in each crystallization step is the composition ratio of the obtained metal composite hydroxide.

[0138] The compounds of metal elements (transition metals) used in adjusting the first raw aqueous solution and the second raw aqueous solution are not particularly limited, but from the perspective of ease of operation, it is preferred to use water-soluble nitrates, sulfates, hydrochlorides, etc. From the perspective of cost and prevention of halogen mixing, it is particularly preferred to use sulfates appropriately.

[0139] In addition, when the metal composite hydroxide contains element M (M is one or more elements selected from Mg, Ca, Al, Ti, V, Cr, Zr, Nb, Mo, Hf and Ta), as the compound for supplying element M, water-soluble compounds are also preferred, for example, magnesium sulfate, calcium sulfate, aluminum sulfate, titanium sulfate, ammonium peroxotitanate, potassium titanium oxalate, vanadium sulfate, ammonium vanadate, chromium sulfate, potassium chromate, zirconium sulfate, niobium oxalate, ammonium molybdate, hafnium sulfate, sodium tantalate, etc. can be suitably used. In addition, the tungsten compound used in the adjustment of the second raw material solution is not particularly limited, for example, sodium tungstate, ammonium tungstate, etc. can be used, preferably sodium tungstate.

[0140] The concentration of the first raw aqueous solution and the second raw aqueous solution is preferably 1 mol / L or more and 2.6 mol / L or less, more preferably 1.5 mol / L or more and 2.2 mol / L or less, based on the total amount of the metal compound. When the concentration of the raw aqueous solution is lower than 1 mol / L, the amount of crystallization in each reaction tank decreases, so the productivity decreases. On the other hand, when the concentration of the mixed aqueous solution exceeds 2.6 mol / L, it exceeds the saturation concentration at room temperature, so the crystals of each metal compound will precipitate again, which may clog the piping, etc.

[0141] It should be noted that the above-mentioned metal compound is not necessarily supplied to the reaction tank in the form of one raw material aqueous solution. For example, when a metal compound that reacts during mixing to generate a compound other than the target compound is used for crystallization reaction, an aqueous solution of the metal compound can also be prepared separately in a manner that the total concentration of the aqueous solution of all metal compounds is within the above range, and the aqueous solution of each metal compound is supplied to the reaction tank in a specified ratio.

[0142] In addition, the supply amount of the first raw material aqueous solution and the second raw material aqueous solution is set so that at the end of the crystallization process, the concentration of the product (the second metal composite hydroxide particles) in the reaction solution (particle growth aqueous solution) is preferably 30 g / L or more and 200 g / L or less, more preferably 80 g / L or more and 150 g / L or less. When the concentration of the product is less than 30 g / L, the aggregation of primary particles sometimes becomes insufficient. On the other hand, when the concentration of the product exceeds 200 g / L, the nucleation aqueous solution or the particle growth aqueous solution cannot be fully diffused in the reaction tank, and sometimes the particle growth will deviate.

[0143] (Alkaline aqueous solution)

[0144] The alkaline aqueous solution for adjusting the pH value in the reaction aqueous solution is not particularly limited, and the common alkali metal hydroxide aqueous solution such as sodium hydroxide and potassium hydroxide can be used. It should be noted that alkali metal hydroxide can also be directly added to the reaction aqueous solution, but from the ease of pH control, it is preferably added in the form of an aqueous solution. In this case, the concentration of the alkali metal hydroxide aqueous solution is preferably set to more than 20 mass % and less than 50 mass %, more preferably set to more than 20 mass % and less than 30 mass %. By limiting the concentration of the alkali metal aqueous solution in such a range, the amount of solvent (water) supplied to the reaction system can be suppressed, and the pH value at the addition position is prevented from becoming locally high, so the metal composite hydroxide particles with narrow particle size distribution can be effectively obtained.

[0145] It should be noted that, for the supply method of the alkaline aqueous solution, as long as the pH value of the reaction aqueous solution does not locally increase and is maintained within a specified range, there is no particular restriction. For example, the reaction aqueous solution can be fully stirred while being supplied by a flow-controllable pump such as a dosing pump.

[0146] (Aqueous solution containing an ammonium ion donor)

[0147] The aqueous solution containing the ammonium ion donor is not particularly limited, and for example, aqueous ammonia, or an aqueous solution of ammonium sulfate, ammonium chloride, ammonium carbonate, or ammonium fluoride can be used.

[0148] As the ammonium root ion donor, when using ammoniacal liquor, its concentration is preferably set to more than 20 mass % and less than 30 mass %, more preferably set to more than 22 mass % and less than 28 mass %. By limiting the concentration of ammoniacal liquor to such a scope, the ammonia loss caused by volatilization etc. can be suppressed to a minimum, so the raising of production efficiency can be achieved. It should be noted that, similarly to the alkaline aqueous solution, the supply method of the aqueous solution comprising the ammonium root ion donor can also be supplied by a pump that can control flow rate.

[0149] (Reaction atmosphere)

[0150] The reaction atmosphere is not particularly limited. For example, when the tap density is 1.20 g / cm 3In the case of the above, metal composite hydroxide with a hollow structure, as described above, it is preferred that the reaction atmosphere in the nucleation process (step S11) is set to an oxidizing atmosphere in which the oxygen concentration exceeds 1% by volume, and the reaction atmosphere in the particle growth process (step S12) is set to a non-oxidizing atmosphere in which the oxygen concentration is less than 1% by volume. When the reaction atmosphere in the reaction tank is made to be the above range, it is possible to easily obtain a metal composite hydroxide with a high tap density and a hollow structure. It should be noted that the switching of the atmosphere can be carried out at the beginning of the particle growth process (step S12), or it can be switched to a non-oxidizing atmosphere during the particle growth process (step S12).

[0151] (Reaction temperature)

[0152] The temperature of the reaction aqueous solution (reaction temperature) is preferably controlled in the range of 20°C or more, more preferably 20°C or more and 60°C or less in the entire crystallization process (nucleation process and particle growth process, second crystallization process). When the reaction temperature is lower than 20°C, nucleation is likely to occur due to the low solubility of the reaction aqueous solution, and it is sometimes difficult to control the average particle size and particle size distribution of the obtained metal composite hydroxide. It should be noted that there is no particular restriction on the upper limit of the reaction temperature, but when it exceeds 60°C, the volatilization of ammonia is promoted, and the amount of the aqueous solution containing the ammonium ion donor supplied for controlling the ammonium ions in the reaction aqueous solution within a certain range increases, and the production cost increases. In addition, when it exceeds 60°C, as previously mentioned, in the nucleation process, strain may occur in the primary crystal and the tap density begins to decrease.

[0153] (Manufacturing equipment)

[0154] In the method for producing the metal composite hydroxide of the present embodiment, it is preferred to use a device that does not recover the product until the reaction is completed, such as an intermittent reaction tank. If such a device is used, since the growing particles and the overflow liquid are not recovered at the same time as in a continuous crystallization device that recovers the product by overflow, it is easy to obtain metal composite hydroxide particles with a narrow particle size distribution.

[0155] In addition, in the manufacturing method of the metal composite hydroxide of the present embodiment, the reaction atmosphere in the crystallization reaction is preferably controlled, so it is preferred to use a device that can control the atmosphere such as a closed device. If it is such a device, the reaction atmosphere in the nucleation process (step S11) and the particle growth process (step S12) can be properly controlled, so it is easy to obtain metal composite hydroxide particles with the above-mentioned particle structure and narrow particle size distribution.

[0156] It should be noted that the composition of the metal composite hydroxide 10 obtained by the manufacturing method of this embodiment is not particularly limited as long as the above-mentioned particle structure, average particle size and particle size distribution can be achieved. For example, the metal composite hydroxide represented by the above-mentioned atomic number ratio (A) can be appropriately used.

[0157] 3. Positive electrode active material for non-aqueous electrolyte secondary batteries

[0158] The positive electrode active material of this embodiment contains a lithium metal composite oxide (hereinafter referred to as "lithium metal composite oxide"), which contains lithium, nickel, manganese and tungsten, and optionally cobalt and element M, and the atomic ratio of each metal element is represented by Li: Ni: Mn: Co: W: M = (1 + u): x: y: z: a: b (x + y + z = 1, -0.05 ≤ u ≤ 0.50, 0.3 ≤ x ≤ 0.95, 0.05 ≤ y ≤ 0.55, 0 ≤ z ≤ 0.4, 0 < a ≤ 0.1, 0 ≤ b ≤ 0.1, M is one or more elements selected from Mg, Ca, Al, Ti, V, Cr, Zr, Nb, Mo, Hf and Ta). In addition, the lithium metal composite oxide has a hexagonal layered crystal structure.

[0159] Figure 5 (A)~ Figure 5 (D) is a schematic diagram showing an example of the lithium metal composite oxide of this embodiment. Figure 5 As shown in (A), the lithium metal composite oxide 20 includes secondary particles 22 formed by agglomerating a plurality of primary particles 21. It should be noted that the lithium metal composite oxide 20 may include a small amount of individual primary particles 21. Figure 5 (A) and Figure 5 (B) The lithium metal composite oxide 20 will be described in detail.

[0160] (compound containing tungsten and lithium)

[0161] For lithium metal composite oxide 20, as Figure 5 As shown in (A), the compound 23 containing tungsten and lithium exists in a concentrated manner on the surface layer of the primary particles 21 existing on the surface or inside of the secondary particles 22 and at the grain boundaries between the primary particles 21. The location where the compound 23 containing tungsten and lithium exists is, for example Fig.10 As shown, this can be confirmed by detecting the W distribution by surface analysis using an energy dispersive X-ray analyzer (EDX). In addition, the compound 23 containing tungsten and lithium preferably exists more on the surface (surface layer) than in the interior of the secondary particle 22 .

[0162] In the case where different compounds cover the surface of the positive electrode active material, the movement (embedding) of lithium ions will be greatly limited, and as a result, the advantage of high capacity of lithium metal composite oxides cannot be fully utilized. In contrast, the compound 23 containing tungsten and lithium (such as lithium tungstate, etc.) has the effect of promoting the movement of lithium ions due to its high conductivity of lithium ions. Therefore, the lithium metal composite oxide 20 forms a compound 23 containing tungsten and lithium on the surface of the primary particles 21 near its surface and at the grain boundaries between the primary particles 21, thereby forming a Li conduction path at the interface with the electrolyte, thereby reducing the reaction resistance of the positive electrode active material and improving the output characteristics. The compound 23 containing tungsten and lithium can exist near the surface of the lithium metal composite oxide 20 in the form of microparticles, for example.

[0163] The compound 23 containing tungsten and lithium is not particularly limited, and examples thereof include lithium tungstates such as Li2WO4, Li4WO5, and Li2W2O7. These lithium tungstates are concentratedly formed on the surface layer of the primary particles 21 present on the surface or inside the secondary particles 22, and on the grain boundaries between the primary particles 21, thereby further improving the lithium ion conductivity of the lithium metal composite oxide 20, and when used in the positive electrode of a secondary battery, the reaction resistance is further reduced.

[0164] (Particle structure)

[0165] The structure of the secondary particles 22 of the lithium metal composite oxide 20 is not particularly limited. For example, the secondary particles 22 may be a solid structure formed by agglomerating the primary particles 21 relatively without gaps, or may be a structure such as Figure 5 (A) shows a void structure with a plurality of voids 24 inside the secondary particle 22. Figure 5 (C) shows a hollow structure having a hollow portion 25. When the lithium metal composite oxide 20 composed of secondary particles having voids 24 and a hollow portion 25 is used as a positive electrode of a secondary battery, the electrolyte penetrates into the interior of the secondary particles 22, and the contact area between the primary particles 21 inside the secondary particles 22 and the electrolyte increases, thereby reducing the resistance inside the secondary particles 22 and improving the output characteristics. In particular, the lithium metal composite oxide 20 obtained by using the metal composite hydroxide 10 having a hollow structure as a precursor maintains the hollow structure that is a characteristic of the metal composite hydroxide 10, and the contact area with the electrolyte increases, so the output characteristics are excellent.

[0166] In addition, if Figure 5As shown in (D), the secondary particle 22 can have a multilayer structure, wherein the multilayer structure has a central portion with a solid structure or a hollow structure, and has a space portion 26 on the outside of the central portion where the primary particles 21 do not exist, and a shell portion (an outer shell portion, or an outer shell portion and an inner shell portion) electrically connected to the central portion (refer to patent document 3). In such a lithium metal composite oxide 20, the space portion 26 does not need to be formed locally, and can also be formed as a whole between the central portion and the inner shell portion or the outer shell portion. In addition, the central portion can also be a state in which multiple aggregation portions formed by aggregation of plate-like primary particles are connected. It should be noted that in this specification, "electrical conduction" means that the high-density portions of the lithium metal composite oxide are directly and structurally connected to each other and are in a state in which electrical conduction can be achieved.

[0167] When the lithium metal composite oxide 20 including the secondary particles 22 having a multilayer structure including the space portion 26 as described above is used as a positive electrode, the electrolyte penetrates into the interior of the secondary particles 22 through the grain boundaries or the space portion 26 between the primary particles 21, so that lithium can be extracted and embedded not only on the surface of the secondary particles 22 but also inside the secondary particles 22. Moreover, the lithium metal composite oxide 20 has a plurality of paths that can be electrically connected to the interior of the secondary particles 22, so that the resistance inside the particles can be made sufficiently small. Therefore, when the lithium metal composite oxide 20 is used to constitute the positive electrode of a secondary battery, the output characteristics can be greatly improved without damaging the capacity characteristics and the cycle characteristics.

[0168] It should be noted that the above-mentioned secondary particles having a multilayer structure including a hollow portion 25 and a space portion 26 can be formed by appropriately adjusting the conditions in the above-mentioned nucleation process (step S11) and the particle growth process (step S12), for example, the conditions described in patent documents 2, 3, etc. can be used.

[0169] In the positive electrode active material of the present embodiment, when manufacturing the secondary particles 22 (metal composite hydroxide) having a multilayer structure including the hollow part 25 and the space part 26, the second crystallization step of adding the tungsten-containing aqueous solution as described above is added to the conventionally known particle growth step, thereby obtaining the metal composite hydroxide 10 having the tungsten concentration layer 3 formed on the surface layer and the lithium metal composite oxide 20 using the metal composite hydroxide 10 as a precursor. In addition, the lithium metal composite oxide 20 can achieve further improvement in output characteristics while maintaining the crystallinity of the positive electrode active material containing the secondary particles 22 having a multilayer structure including the hollow part 25 and the space part 26 by the presence of the compound 23 containing lithium and tungsten on the surface layer of the primary particles 21 and at the grain boundaries between the primary particles 21.

[0170] (Average particle size)

[0171] The average particle size (MV) of the positive electrode active material of this embodiment is not particularly limited, for example, it can be adjusted to be greater than 3 μm and less than 9 μm. When the average particle size is within the above range, not only can the battery capacity per unit volume of the secondary battery using the positive electrode active material be increased, but also the thermal stability and output characteristics can be improved. In contrast, when the average particle size is less than 4 μm, the filling property of the positive electrode active material is reduced, and it is difficult to increase the battery capacity per unit volume. When the average particle size exceeds 9 μm, the reaction area of ​​the positive electrode active material begins to decrease, so the output characteristics sometimes become insufficient.

[0172] As with the above-mentioned metal composite hydroxide, the average particle size of the positive electrode active material refers to a volume-based average particle size (MV), which can be determined based on, for example, a volume integrated value measured using a laser diffraction scattering particle size analyzer.

[0173] (Particle size distribution)

[0174] For the positive electrode active material of this embodiment, the index indicating the width of the particle size distribution, namely [(d90-d10) / average particle size], is preferably 0.65 or less. When [(d90-d10) / average particle size] is within the above range, the lithium metal composite oxide 20 having a very narrow particle size distribution can be formed. In such a positive electrode active material, the proportion of fine particles or coarse particles is small, and the thermal stability, cycle characteristics, and output characteristics of the secondary battery using it as the positive electrode are excellent.

[0175] On the other hand, when [(d90-d10) / average particle size] exceeds 0.65, the proportion of fine particles or coarse particles in the positive electrode active material increases. In a secondary battery using a positive electrode active material with a wide particle size distribution, for example, heat is generated due to a local reaction of fine particles, the thermal stability is reduced, and the fine particles selectively deteriorate, and sometimes the cycle characteristics are reduced. In addition, a secondary battery using a positive electrode active material with a wide particle size distribution cannot fully ensure the reaction area between the electrolyte and the positive electrode active material due to the large proportion of coarse particles, and sometimes the output characteristics are reduced.

[0176] It should be noted that, in the case of industrial-scale production as a prerequisite, it is unrealistic to use a material that is too small [(d90-d10) / average particle size] as a positive electrode active material. Therefore, considering cost and productivity, the lower limit of [d90-d10] / average particle size] is preferably set to about 0.25. In addition, the meaning of d10 and d90 in [(d90-d10) / average particle size] and their method of obtaining are the same as those of the above-mentioned metal composite hydroxides.

[0177] (Tap density)

[0178] The tap density of the positive electrode active material of this embodiment is not particularly limited. For example, when the secondary particles 2 have a hollow structure, it is preferably 1.2 g / cm 3 Above 1.99g / cm 3 Below, more preferably 1.2 g / cm 3 Above and 1.9g / cm 3 Below, more preferably 1.3 g / cm 3 Above and 1.7g / cm 3 When the tap density is within the above range, the positive electrode active material has a hollow structure suitable for use in the positive electrode of a secondary battery, the battery capacity per unit volume is increased, and the contact area with the electrolyte is increased to improve the output characteristics. On the other hand, when the tap density exceeds 1.99 g / cm 3 When the particle size distribution is large, the hollow part in the particle structure is small, and the average particle size tends to increase, and the output characteristics decrease with the decrease in the reaction area. In addition, when the width of the particle size distribution is large, the tap density tends to increase, but in this case, the fine particles will selectively deteriorate and the cycle characteristics will decrease. On the other hand, the tap density is less than 1.2g / cm 3 When the tap density is low, the hollow part of the particle structure increases, the particle strength decreases, and thus the cycle characteristics sometimes decrease. In addition, when the tap density is low, the filling property of the positive electrode active material decreases, making it difficult to increase the battery capacity per unit volume.

[0179] (Sintering Aggregation)

[0180] For the positive electrode active material of the present embodiment, the index indicating the degree of sintering and aggregation of particles, namely [d50 of lithium metal composite oxide / d50 of metal composite hydroxide] (hereinafter referred to as "d50 ratio"), is preferably in the range of 0.95 or more and 1.05 or less. When the d50 ratio is within the above range, the positive electrode active material can be composed of lithium metal composite oxide 20 in which secondary particles are almost not aggregated with sintering and aggregation. The secondary battery using such a positive electrode active material has high filling property, high capacity, less deviation in characteristics, and excellent uniformity.

[0181] On the other hand, when the d50 ratio exceeds 1.05, the specific surface area is sometimes reduced or the filling property is reduced as the particles are sintered and aggregated. The reactivity of the secondary battery using such a positive electrode active material is reduced, resulting in reduced output characteristics, and the capacity is sometimes reduced. In addition, when the secondary battery using such a positive electrode active material is repeatedly charged and discharged, in the positive electrode, the weak part of the secondary particles aggregated from each other selectively disintegrates, and therefore sometimes becomes the main cause of greater damage to the cycle characteristics.

[0182] In addition, when the d50 ratio is less than 1.0, it means that the particle size is reduced by crushing the lithium metal composite oxide 20, and part of the primary particles 21 fall off from the secondary particles 22. In particular, when the d50 ratio is less than 0.95, a large amount of fine powder is generated due to the large amount of primary particles 21 falling off, and the particle size distribution sometimes becomes broad.

[0183] It should be noted that the d50 of the metal composite hydroxide refers to the d50 of the metal composite hydroxide 10 used as a precursor when manufacturing the lithium metal composite oxide 20. In addition, the d50 of the lithium metal composite oxide 20 and the metal composite hydroxide 10 can be measured using a laser diffraction scattering particle size analyzer, which refers to the particle size when the cumulative volume of the number of particles of each particle size accumulated from the side with a smaller particle size reaches 50% of the total volume of all particles.

[0184] (Crystallite diameter)

[0185] Compared with the positive electrode active material as a precursor of a metal composite hydroxide obtained by uniformly adding tungsten throughout the crystallization process as in the previous manufacturing method, the positive electrode active material of the present embodiment can further increase the crystallite diameter of the (003) plane obtained by powder X-ray diffraction measurement. The crystallite diameter of the (003) plane of the positive electrode active material can be set to, for example, 110nm or more, preferably adjusted to 120nm or more. In the case where the crystallite diameter of the (003) plane of the positive electrode active material is 120nm or more, the crystallinity is high, and the reaction resistance of the secondary battery using the positive electrode active material as the positive electrode decreases, thereby improving the output characteristics, and in addition, the thermal stability is also improved. On the other hand, when the crystallite diameter of the (003) plane is less than 120nm, the thermal stability of the secondary battery is sometimes reduced. It should be noted that the upper limit of the crystallite diameter of the (003) plane is not particularly limited, for example, it can be set to 200nm or less, preferably 120nm or more and 150nm or less. In the positive electrode active material of the present embodiment, by using the metal composite hydroxide 10 having the tungsten concentration layer 3 on the surface as a precursor as described above, high crystallinity can be maintained, and thus the crystallite diameter of the (003) plane can be within the above range.

[0186] (composition)

[0187] As long as the positive electrode active material of this embodiment has the above-mentioned characteristics, its composition is not particularly limited. For example, it contains lithium, nickel, manganese and tungsten, and optionally cobalt and element M, and the atomic ratio (B) of each metal element is represented by Li: Ni: Mn: Co: W: M = (1 + u): x: y: z: a: b (x + y + z = 1, -0.05 ≤ u ≤ 0.50, 0.3 ≤ x ≤ 0.95, 0.05 ≤ y ≤ 0.55, 0 ≤ z ≤ 0.4, 0 < a ≤ 0.1, 0 ≤ b ≤ 0.1, M is one or more elements selected from Mg, Ca, Al, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta). In the above-mentioned atomic ratio (B), the preferred range of the composition of each element and its meaning are the same as the following general formula (B). Therefore, the description of these matters is omitted here.

[0188] In addition, the positive electrode active material of this embodiment may also be represented by the general formula (B): Li 1+u Ni x Mn y Co z W a M b O2 (-0.05≤u≤0.50, x+y+z=1, 0.3≤x≤0.95, 0.05≤y≤0.55, 0≤z≤0.4, 0<a≤0.1, 0≤b≤0.1, M is one or more elements selected from Mg, Ca, Al, Ti, V, Cr, Zr, Nb, Mo, Hf and Ta).

[0189] In the above-mentioned general formula (B), the value of u representing the range of the content (1+u) of lithium (Li) is preferably greater than -0.05 and less than 0.50, more preferably greater than 0 and less than 0.50, and further preferably greater than 0 and less than 0.35. When the value of u is in the above-mentioned range, the output characteristics and capacity characteristics of the secondary battery using the positive electrode active material as the positive electrode material can be improved. In contrast, when the value of u is less than -0.05, the positive electrode resistance of the secondary battery becomes large and the output characteristics cannot be improved. On the other hand, when the value of u exceeds 0.50, the initial discharge capacity is sometimes reduced or the positive electrode resistance becomes large.

[0190] In the above general formula (B), the value x representing the nickel (Ni) content is preferably 0.3 or more and 0.95 or less, more preferably 0.3 or more and 0.9 or less. Nickel is an element that contributes to the high potential and high capacity of secondary batteries. When the value of x is less than 0.3, the capacity characteristics of the secondary battery using the positive electrode active material cannot be improved. On the other hand, when the value of x exceeds 0.95, the content of other elements is reduced, and the effects of other elements cannot be obtained.

[0191] In the above general formula (B), the value y representing the content of manganese (Mn) is preferably 0.05 or more and 0.55 or less, more preferably 0.10 or more and 0.40 or less. Manganese is an element that helps to improve thermal stability. When the value of y is less than 0.05, the thermal stability of the secondary battery using the positive electrode active material cannot be improved. On the other hand, when the value of y exceeds 0.55, Mn is dissolved from the positive electrode active material during high temperature operation, and sometimes the charge and discharge cycle characteristics are deteriorated.

[0192] In the above general formula (B), the value of z representing the content of cobalt (Co) is preferably greater than 0 and less than 0.4, and more preferably greater than 0.10 and less than 0.35. Cobalt is an element that helps improve the charge and discharge cycle characteristics. When the value of z exceeds 0.4, the initial discharge capacity of the secondary battery using the positive electrode active material is sometimes greatly reduced.

[0193] In the above general formula (B), the value of a representing the content of tungsten (W) is greater than 0 and less than 0.1, preferably greater than 0.001 and less than 0.01, and more preferably greater than 0.0045 and less than 0.006, when the total number of moles of Ni, Co and Mn is set to 1. When the value of a is within the above range, the positive electrode active material has better output characteristics and cycle characteristics while maintaining high crystallinity. In addition, as described above, W is mainly contained in the surface layer of the primary particle 21 near the surface of the secondary particle 22 in the positive electrode active material, or the grain boundary between the primary particles 21.

[0194] In the positive electrode active material of this embodiment, in order to further improve the durability and output characteristics of the secondary battery, in addition to the above-mentioned metal elements, an element M may also be contained. As such an element M, one or more selected from magnesium (Mg), calcium (Ca), aluminum (Al), titanium (Ti), vanadium (V), chromium (Cr), zirconium (Zr), niobium (Nb), molybdenum (Mo), hafnium (Hf) and tantalum (Ta) can be used.

[0195] In the above general formula (B), the value of b representing the content of the element M is preferably 0 or more and 0.1 or less, more preferably 0 or more and 0.05 or less, and further preferably 0.001 or more and 0.05 or less, when the total number of moles of Ni, Co and Mn is 1. When the value of b exceeds 0.1, the metal elements contributing to the Redox (oxidation-reduction) reaction decrease, and thus the battery capacity may decrease.

[0196] In the positive electrode active material represented by the general formula (B), it is preferred that the composition be the general formula (B1): Li 1+u Ni x Mn y Co z W a Mb O2 (-0.05≤u≤0.20, x+y+z=1, 0.7<x≤0.95, 0.05≤y≤0.1, 0≤z≤0.2, 0<a≤0.1, 0≤b≤0.1, M is one or more elements selected from Mg, Ca, Al, Ti, V, Cr, Zr, Nb, Mo, Hf and Ta). Among them, from the viewpoint of taking both thermal stability and battery capacity into consideration, it is more preferred to make the value of x in the above general formula (B1) 0.7<x≤0.9, and further preferably 0.7<x≤0.85.

[0197] In addition, from the viewpoint of further improving thermal stability, it is preferred that the composition be of the general formula (B2): Li 1+ u Ni x Mn y Co z W a M b O2 (-0.05≤u≤0.50, x+y+z=1, 0.3≤x≤0.7, 0.1≤y≤0.55, 0≤z≤0.4, 0<a≤0.1, 0≤b≤0.1, M is one or more elements selected from Mg, Ca, Al, Ti, V, Cr, Zr, Nb, Mo, Hf and Ta).

[0198] 4. Method for producing positive electrode active material for non-aqueous electrolyte secondary battery

[0199] Figure 6 1 is a diagram showing an example of a method for producing a positive electrode active material according to the present embodiment. The production method according to the present embodiment can easily produce a positive electrode active material including the above-mentioned lithium metal composite oxide 20 on an industrial scale. It should be noted that the positive electrode active material including the lithium metal composite oxide 20 is not particularly limited as long as it has the above-mentioned specific structure, average particle size and particle size distribution, and can be obtained using a known production method.

[0200] like Figure 6 As shown, the method for producing a positive electrode active material of the present embodiment comprises the following steps: a step of mixing the metal composite hydroxide 10 obtained by the above-mentioned production method with a lithium compound to obtain a lithium mixture (step S30); and a step of calcining the lithium mixture to obtain a lithium metal composite oxide 20 (step S40). In addition, as required, in addition to the above-mentioned steps, a heating treatment step, a pre-calcining step, and the like may be added.

[0201] The tungsten in the tungsten concentrated layer 3 formed on the surface of the metal composite hydroxide 10 reacts with the lithium compound in the mixing step (step S30) and the calcining step (step S40), and forms a compound 23 containing tungsten and lithium on the surface of the primary particles 21 in the lithium metal composite oxide 20 and at the grain boundaries between the primary particles 21. Figure 6 , an example of a method for producing the positive electrode active material according to this embodiment is described.

[0202] (Mixing process)

[0203] First, at least one of the metal composite hydroxide 10 and the metal composite oxide obtained by heat-treating the metal composite hydroxide (hereinafter collectively referred to as a “precursor”) is mixed with a lithium compound to obtain a lithium mixture (step S30 ).

[0204] In the mixing step (step S30), the precursor and the lithium compound are mixed in such a manner that the ratio (Li / Me) of the sum of the number of metal atoms other than lithium in the lithium mixture, specifically nickel, cobalt and manganese atoms (Me) to the number of lithium atoms (Li) is 0.95 or more and 1.5 or less, preferably 1.0 or more and 1.5 or less, more preferably 1.0 or more and 1.35 or less, and further preferably 1.0 or more and 1.2 or less. That is, since Li / Me does not change before and after the calcination step (step S40), the precursor and the lithium compound are mixed in such a manner that the Li / Me in the mixing step is the Li / Me of the target positive electrode active material.

[0205] The lithium compound used in the mixing step (step S30) is not particularly limited, and lithium hydroxide, lithium nitrate, lithium carbonate or a mixture thereof is preferably used from the viewpoint of ease of acquisition. In particular, lithium hydroxide or lithium carbonate is preferably used in view of ease of operation and stability of quality.

[0206] The precursor and the lithium compound are preferably mixed sufficiently to prevent the generation of fine powder. If the mixing is insufficient, the Li / Me ratio between the particles may deviate, and sufficient battery characteristics may not be obtained. It should be noted that a general mixer may be used for the mixing. For example, a vibration mixer (shaker mixer), a Loedige mixer, a Julia mixer, a V-type mixer, etc. may be used.

[0207] (Heat treatment process)

[0208] It should be noted that, in the method for manufacturing the positive electrode active material of the present embodiment, a heat treatment step may be optionally provided before the mixing step (step S30), and the metal composite hydroxide 10 may be mixed with the lithium compound after heat treatment (not shown). Here, the particles obtained after the heat treatment step include not only particles of the metal composite hydroxide 10 from which at least a portion of the remaining water has been removed in the heat treatment step, but also particles of the metal composite oxide converted from the hydroxide to the oxide by the heat treatment step, or a mixture thereof.

[0209] The heat treatment step is a step of removing excess water contained in the metal composite hydroxide 10 by heating the metal composite hydroxide 10 to 105° C. or higher and 750° C. or lower. This can reduce the amount of water remaining after the calcination step to a certain level, and can suppress the variation in the composition of the obtained positive electrode active material.

[0210] The heat treatment temperature in the heat treatment step is set to be 105° C. or higher and 750° C. or lower. When the heat treatment temperature is lower than 105° C., the excess water in the metal composite hydroxide 10 cannot be sufficiently removed, and sometimes the deviation cannot be sufficiently suppressed. On the other hand, even if the heat treatment temperature exceeds 700° C., not only can no further effect be expected, but also the production cost will increase.

[0211] It should be noted that, in the heat treatment process, as long as the water can be removed to the extent that the ratio of the number of atoms of each metal component and the number of atoms of Li in the positive electrode active material does not deviate, it is not necessarily necessary to convert all of the metal composite hydroxide 10 into a composite oxide. However, in order to further reduce the deviation of the ratio of the number of atoms of each metal component and the number of atoms of Li, it is preferably heated to 400° C. or more to convert all of the metal composite hydroxide 10 into a composite oxide. It should be noted that the above deviation can be further suppressed by analyzing the metal components contained in the metal composite hydroxide 10 based on the heat treatment conditions in advance and determining the mixing ratio with the lithium compound.

[0212] The atmosphere for performing the heat treatment is not particularly limited as long as it is a non-reducing atmosphere, but it is preferably performed in an air flow which is easy to realize.

[0213] The heat treatment time is not particularly limited, but is preferably at least 1 hour or longer, more preferably 5 hours or longer and 15 hours or shorter, from the viewpoint of sufficiently removing excess moisture in the metal composite hydroxide 10 .

[0214] (Baking process)

[0215] Next, the lithium mixture obtained in the mixing step (step S30) is calcined to obtain the lithium metal composite oxide 20 (step S40). In this step, calcination is performed under predetermined conditions to diffuse lithium in the precursor, thereby obtaining the lithium metal composite oxide 20. The obtained lithium metal composite oxide 20 can be used directly as a positive electrode active material, or it can be used as a positive electrode active material after adjusting the particle size distribution through a crushing step as described later.

[0216] [Calcination temperature]

[0217] The calcination temperature of the lithium mixture is preferably set to 650° C. or higher and 980° C. or lower. When the calcination temperature is lower than 650° C., lithium cannot be sufficiently diffused in the precursor, and the remaining lithium, unreacted metal composite hydroxide 10 or lithium metal composite oxide 20 remain, or the crystallinity of the obtained lithium metal composite oxide 20 becomes insufficient. On the other hand, when the calcination temperature exceeds 980° C., the lithium composite oxide particles are sintered violently, resulting in abnormal particle growth, and the proportion of amorphous coarse particles may increase.

[0218] It should be noted that, when the positive electrode active material represented by the general formula (B1) is to be obtained, the calcination temperature is preferably set to 650° C. or more and 900° C. or less. On the other hand, when the positive electrode active material represented by the general formula (B2) is to be obtained, the calcination temperature is preferably set to 800° C. or more and 980° C. or less.

[0219] In addition, the heating rate in the roasting process (step S40) is preferably set to 2°C / minute or more and 10°C / minute or less, and more preferably 5°C / minute or more and 10°C / minute or less. In addition, in the roasting process (step S40), it is also possible to keep preferably 1 hour or more and 5 hours or less, and more preferably 2 hours or more and 5 hours or less at a temperature near the melting point of the lithium compound used. Thus, the precursor and the lithium compound can react more uniformly.

[0220] [Baking time]

[0221] The holding time (baking time) at the above-mentioned calcination temperature is preferably set to at least 2 hours, more preferably 4 hours and less than 24 hours. If the holding time at the calcination temperature is less than 2 hours, lithium cannot be fully diffused in the precursor, and there is a concern that the remaining lithium, unreacted precursor particles remain, or the crystallinity of the particles of the obtained lithium metal composite oxide 20 becomes insufficient.

[0222] It should be noted that after the holding time is over, the cooling rate from the roasting temperature to at least 200°C is preferably set to 2°C / minute or more and 10°C / minute or less, more preferably 3°C / minute or more and 7°C / minute or less. By controlling the cooling rate to such a range, productivity can be ensured, and equipment such as saggers can be prevented from being damaged by rapid cooling.

[0223] [Baking atmosphere]

[0224] The atmosphere during calcination is preferably an oxidizing atmosphere, more preferably an atmosphere having an oxygen concentration of 18% by volume or more and 100% by volume or less, and particularly preferably a mixed atmosphere of oxygen and an inert gas at the above oxygen concentration. That is, calcination is preferably performed in the atmosphere or even in an oxygen gas flow. When the oxygen concentration is lower than 18% by volume, the crystallinity of the particles of the lithium metal composite oxide 20 may become insufficient.

[0225] It should be noted that the furnace used in the roasting process (step S40) is not particularly limited, as long as it can be a furnace that heats the lithium mixture in the atmosphere and even in an oxygen gas flow. However, from the viewpoint of keeping the furnace atmosphere uniform, it is preferred that there is no electric furnace generated by gas, and an intermittent or continuous electric furnace can be used appropriately. In this regard, the furnace used in the heat treatment process (step S20) and the pre-baking process described later is also the same.

[0226] (Pre-baking process)

[0227] It should be noted that, when lithium hydroxide or lithium carbonate is used as the lithium compound, a pre-baking process can be performed after the mixing process (step S30) and before the calcination process (step S40). The pre-baking process is a process of pre-baking the lithium mixture at a temperature lower than the calcination temperature described later, and at a temperature of 350°C to 800°C, preferably 450°C to 780°C. Thus, lithium can be fully diffused in the precursor, and more uniform lithium metal composite oxide particles can be obtained.

[0228] It should be noted that the holding time at the above temperature is preferably set to more than 1 hour and less than 10 hours, preferably set to more than 3 hours and less than 6 hours. In addition, the atmosphere in the pre-baking process is the same as the baking process described later, preferably set to an oxidizing atmosphere, more preferably set to an atmosphere with an oxygen concentration of more than 18 volume % and less than 100 volume %.

[0229] (Crushing process)

[0230] The lithium metal composite oxide 20 obtained by the calcination process (step S40) sometimes aggregates or slightly sinters. In this case, it is preferred to crush the aggregates or sintered bodies of the particles of the lithium metal composite oxide 20. Thus, the average particle size and particle size distribution of the obtained positive electrode active material can be adjusted to a suitable range. It should be noted that crushing refers to the operation of applying mechanical energy to the aggregates formed by multiple secondary particles 22 produced by sintering necking between the secondary particles 22 during calcination, so that the secondary particles are separated without substantially destroying the secondary particles themselves, and disassembling the aggregates.

[0231] As a method for crushing, a known method can be used, for example, a pin mill, a hammer mill, etc. It should be noted that at this time, it is preferable to adjust the crushing force to an appropriate range so as not to destroy the secondary particles.

[0232] 5. Non-aqueous electrolyte secondary battery

[0233] The nonaqueous electrolyte secondary battery of the present embodiment has a positive electrode containing the above-mentioned positive electrode active material as a positive electrode material. The nonaqueous electrolyte secondary battery can have the same components as a general nonaqueous electrolyte secondary battery, such as a positive electrode, a negative electrode, a separator, a nonaqueous electrolyte, etc., for example, a positive electrode, a negative electrode and a nonaqueous electrolyte. In addition, the nonaqueous electrolyte secondary battery can also have, for example, a positive electrode, a negative electrode and a solid electrolyte. It should be noted that the embodiments described below are only illustrative, and the nonaqueous electrolyte secondary battery of the present invention can also be applied to various changes and improved methods based on the embodiments described in this specification.

[0234] (1) Components

[0235] (positive electrode)

[0236] Using the positive electrode active material for a nonaqueous electrolyte secondary battery obtained in this embodiment, a positive electrode for a nonaqueous electrolyte secondary battery is produced, for example, in the following manner.

[0237] First, the conductive material and the binder are mixed with the obtained powdered positive electrode active material, and activated carbon and solvents for viscosity adjustment are further added as needed, and they are kneaded to make a positive electrode composite material paste. At this time, each mixing ratio in the positive electrode composite material paste is also an important factor in determining the performance of the non-aqueous electrolyte secondary battery. For example, when the solid content of the positive electrode composite material excluding the solvent is set to 100 parts by mass, the content of the positive electrode active material can be set to 60 parts by mass to 95 parts by mass, the content of the conductive material is set to 1 part by mass to 20 parts by mass, and the content of the binder is set to 1 part by mass to 20 parts by mass, as with the positive electrode of a general non-aqueous electrolyte secondary battery.

[0238] The obtained positive electrode composite material paste is applied to the surface of a collector such as aluminum foil and dried to volatilize the solvent. As needed, in order to increase the electrode density, it is sometimes pressed by a roller press or the like. Thus, a sheet-like positive electrode can be made. The sheet-like positive electrode can be cut into appropriate sizes according to the target battery, and is provided for the production of the battery. However, the production method of the positive electrode is not limited to the above-mentioned exemplified method, and can also be based on other methods.

[0239] As the conductive material, for example, graphite (natural graphite, artificial graphite, expanded graphite, etc.); carbon black materials such as acetylene black and Ketjen black can be used.

[0240] The binder is a substance that plays a role in binding and fixing the active material particles, and examples thereof include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), fluororubber, ethylene propylene diene rubber, styrene butadiene, cellulose resin, and polyacrylic acid.

[0241] In addition, as required, a solvent for dispersing the positive electrode active material, the conductive material and the activated carbon and dissolving the binder can be added to the positive electrode composite material. As a solvent, an organic solvent such as N-methyl-2-pyrrolidone can be used. In addition, in order to increase the electric double layer capacity, activated carbon can also be added to the positive electrode composite material.

[0242] (negative electrode)

[0243] Negative electrode: metallic lithium, lithium alloy, etc.; or a negative electrode composite material prepared by mixing a binder with a negative electrode active material capable of absorbing and deintercalating lithium ions and adding an appropriate solvent to form a paste, which is applied to the surface of a metal foil collector such as copper and dried, and compressed as needed to increase the electrode density.

[0244] As the negative electrode active material, for example, lithium-containing materials such as metallic lithium and lithium alloys; calcined organic compounds such as natural graphite, artificial graphite and phenolic resin that can absorb and release lithium ions; and powders of carbon materials such as coke. In this case, as the negative electrode binder, fluorine-containing resins such as PVDF can be used, as with the positive electrode, and organic solvents such as N-methyl-2-pyrrolidone can be used as solvents for dispersing these active materials and binders. In addition, as a binder, in addition to the above-mentioned organic binders such as PVDF, water-based binders such as styrene-butadiene rubber can also be used. In addition, the water-based binder can also use carboxymethyl cellulose (CMC) as a viscosity modifier. For example, a water-based binder with styrene-butadiene latex as the main additive and CMC as a viscosity modifier can increase the bonding force with a small amount.

[0245] (Separator)

[0246] The separator is arranged in a manner sandwiched between the positive electrode and the negative electrode, and has the function of separating the positive electrode from the negative electrode and retaining the electrolyte. As such a separator, for example, a film of polyethylene, polypropylene, etc., and a film having a large number of fine pores can be used, but there is no particular limitation as long as it has the above-mentioned function.

[0247] (Non-aqueous electrolyte)

[0248] As the non-aqueous electrolyte, a non-aqueous electrolyte can be used. The non-aqueous electrolyte is obtained by dissolving a lithium salt as a supporting electrolyte in an organic solvent. In addition, as the non-aqueous electrolyte, a non-aqueous electrolyte in which a lithium salt is dissolved in an ionic liquid can also be used. It should be noted that an ionic liquid refers to a salt composed of cations and anions other than lithium ions and also appears in a liquid state at room temperature.

[0249] As the organic solvent, one selected from the following substances can be used alone or in combination of two or more thereof: cyclic carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate and trifluoropropylene carbonate; chain carbonates such as diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate and dipropyl carbonate; ether compounds such as tetrahydrofuran, 2-methyltetrahydrofuran and dimethoxyethane; sulfur compounds such as ethyl methyl sulfone and butane sultone; phosphorus compounds such as triethyl phosphate and trioctyl phosphate, etc.

[0250] As supporting electrolytes, LiPF6, LiBF4, LiClO4, LiAsF6, LiN(CF3SO2)2, and complex salts thereof can be used.

[0251] Furthermore, the non-aqueous electrolyte may contain a radical scavenger, a surfactant, a flame retardant, and the like.

[0252] In addition, a solid electrolyte may be used as the non-aqueous electrolyte. A solid electrolyte has the property of being able to withstand high voltage. Examples of the solid electrolyte include inorganic solid electrolytes and organic solid electrolytes.

[0253] As the inorganic solid electrolyte, an oxide-based solid electrolyte, a sulfide-based solid electrolyte, or the like can be used.

[0254] The oxide-based solid electrolyte is not particularly limited, and any substance containing oxygen (O) and having lithium ion conductivity and electronic insulation can be used. Examples of the oxide-based solid electrolyte include lithium phosphate (Li3PO4), Li3PO4N X 、LiBO2N X, LiNbO3, LiTaO3, Li2SiO3, Li4SiO4-Li3PO4, Li4SiO4-Li3VO4, Li2O-B2O3-P2O5, Li2O-SiO2, Li2O-B2O3-ZnO, Li 1+X Al X Ti 2-X (PO4)3(0≤X≤1), Li 1+X Al X Ge 2-X (PO4)3(0≤X≤1), LiTi2(PO4)3, Li 3X La 2 / 3-X TiO3(0≤X≤2 / 3), Li5La3Ta2O 12 、Li7La3Zr2O 12 、Li6BaLa2Ta2O 12 , Li 3.6 Si 0.6 P 0.4 O4, etc.

[0255] Sulfide-based solid electrolytes are not particularly limited, and any substance containing sulfur (S) and having lithium ion conductivity and electronic insulation can be used. Examples of sulfide-based solid electrolytes include Li2S-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-B2S3, Li3PO4-Li2S-Si2S, Li3PO4-Li2S-SiS2, LiPO4-Li2S-SiS, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, and the like.

[0256] It should be noted that as the inorganic solid electrolyte, substances other than those listed above may be used, for example, Li3N, LiI, Li3N-LiI-LiOH, etc. may be used.

[0257] As an organic solid electrolyte, there is no particular limitation as long as it is a polymer compound showing ionic conductivity, and for example, polyethylene oxide, polypropylene oxide, copolymers thereof, etc. can be used. In addition, the organic solid electrolyte may also contain a supporting electrolyte (lithium salt). It should be noted that, when a solid electrolyte is used, in order to ensure contact between the electrolyte and the positive electrode active material, a solid electrolyte may also be mixed in the positive electrode material.

[0258] (2) Non-aqueous electrolyte secondary battery

[0259] The nonaqueous electrolyte secondary battery of this embodiment, which is composed of the positive electrode, the negative electrode, the separator and the nonaqueous electrolyte solution or the positive electrode, the negative electrode and the solid electrolyte as described above, can be formed into various shapes such as a cylindrical shape and a stacked shape.

[0260] When a non-aqueous electrolyte is used as the non-aqueous electrolyte, the positive electrode and the negative electrode are stacked with a separator to form an electrode body, the non-aqueous electrolyte is impregnated into the obtained electrode body, the positive electrode collector is connected to the positive terminal connected to the outside, and the negative electrode collector is connected to the negative terminal connected to the outside with a collecting lead, etc., and the battery case is sealed to complete the non-aqueous electrolyte secondary battery.

[0261] (3) Characteristics of non-aqueous electrolyte secondary batteries

[0262] As described above, the nonaqueous electrolyte secondary battery of the present invention uses the above-mentioned positive electrode active material as the positive electrode material, so it is excellent in capacity characteristics, output characteristics and cycle characteristics. Moreover, compared with the secondary battery using the positive electrode active material composed of lithium nickel oxide particles in the past, it can be said that the thermal stability is also excellent.

[0263] (4) Application

[0264] As mentioned above, the capacity characteristic, output characteristic and cycle characteristic of the nonaqueous electrolyte secondary battery of the present invention are excellent, and can be applicable to the power supply of small portable electronic equipment (notebook type personal computer, telephone terminal etc.) requiring these characteristics at a high level. In addition, the thermal stability of the nonaqueous electrolyte secondary battery of the present invention is also excellent, and not only can realize miniaturization and high output, but also can simplify expensive protection circuit, and therefore can also be applicable to the power supply of the transportation equipment (such as vehicle drive power supply etc.) that is restricted as the carrying space.

[0265] Example

[0266] Hereinafter, the present invention will be described using examples and comparative examples. It should be noted that, in the following examples and comparative examples, unless otherwise specified, each sample of a special grade reagent manufactured by Wako Pure Chemical Industries, Ltd. is used in the preparation of metal composite hydroxides and positive electrode active materials. In addition, by the nucleation process and the particle growth process, the pH value of the reaction aqueous solution is measured by a pH controller (Nippon Rika, NPH-690D), and the supply of the sodium hydroxide aqueous solution is adjusted based on the measured value, so that the pH value of the reaction aqueous solution in each process is controlled to be within the range of ±0.2.

[0267] (Example 1)

[0268] (a) Production of Metal Composite Hydroxides

[0269] [Nucleation process]

[0270] First, 1.2 L of water was added to the reaction tank and stirred at 790 rpm while the temperature in the tank was set to 40° C. At this time, oxygen was introduced into the reaction tank and circulated for 30 minutes to make the reaction atmosphere an oxidizing atmosphere with an oxygen concentration exceeding 1% by volume. Next, 25% by mass sodium hydroxide aqueous solution and 25% by mass ammonia water were appropriately supplied to the reaction tank and adjusted so that the pH value was 12.5 based on a liquid temperature of 25° C. and the ammonium ion concentration was 10 g / L, thereby forming a pre-reaction aqueous solution.

[0271] At the same time, nickel sulfate, cobalt sulfate, manganese sulfate, and zirconium sulfate were dissolved in water so that the molar ratio of the metal elements was Ni:Mn:Co:Zr=38:30:32:0.2 to prepare a 2 mol / L first raw material aqueous solution.

[0272] Next, the first raw material aqueous solution was supplied to the pre-reaction aqueous solution at 13 ml / min to form an aqueous solution for the nucleation process, and nucleation was performed for 2.5 minutes. At this time, 25% by mass sodium hydroxide aqueous solution and 25% by mass ammonia water were supplied in a timely manner to maintain the pH value and ammonium ion concentration of the aqueous solution for nucleation within the above range.

[0273] [Particle Growth Process]

[0274] After nucleation is completed, the supply of all aqueous solutions is temporarily stopped, and sulfuric acid is added to the reaction tank to adjust the pH to 11.6 based on a liquid temperature of 25° C., thereby forming an aqueous solution for particle growth. After confirming that the pH has reached a specified value, the first raw material aqueous solution is supplied to the reaction tank to grow the nuclei (particles) generated in the nucleation step.

[0275] In order to make the reaction tank a non-oxidizing atmosphere in the middle of the particle growth process, the supply of the raw aqueous solution is temporarily stopped, and nitrogen is introduced instead of oxygen. When the reaction atmosphere forms a non-oxidizing atmosphere with an oxygen concentration of less than 1 volume %, the supply of the first raw aqueous solution is restarted.

[0276] [Second Crystallization Step]

[0277] As the second raw material aqueous solution, the first raw material aqueous solution and the aqueous solution containing tungsten are used. As the aqueous solution containing tungsten, sodium tungstate dihydrate is dissolved in water so that the molar ratio of each metal element of the obtained hydroxide is Ni:Co:Mn:Zr:W=38:30:32:0.2:0.5 to prepare the sodium tungstate aqueous solution.

[0278] From the moment when 19 / 20 of the total time for particle growth (95%) has passed, the first aqueous solution is supplied, and the sodium tungstate aqueous solution (addition range: 5%) is supplied to the reaction tank. The supply of all aqueous solutions is stopped, thereby ending the particle growth process. The obtained product is then washed, filtered and dried to obtain a powdered metal composite hydroxide.

[0279] It should be noted that, in the particle growth step in the first crystallization step and the second crystallization step, 25% by mass of sodium hydroxide aqueous solution and 25% by mass of ammonia water are supplied in a timely manner through these steps to maintain the pH value and ammonium ion concentration of the aqueous solution for particle growth within the above range. In addition, for the reaction atmosphere, nitrogen gas is introduced to adjust the non-oxidizing atmosphere with an oxygen concentration of less than 1% by volume. It should be noted that the supply rate of the first raw material aqueous solution is set to be constant (13 ml / min) throughout the crystallization step.

[0280] (b) Evaluation of Metal Composite Hydroxides

[0281] By analyzing with an ICP emission spectrometer (manufactured by Shimadzu Corporation, ICPE-9000), it was confirmed that the metal composite hydroxide consisted of the general formula: Ni 0.38 Mn 0.30 Co 0.32 Zr 0.002 W 0.005 (OH)2 represents.

[0282] In addition, use laser diffraction scattering type particle size analyzer (made by Nikki Co., Ltd., MicrotracHRA), measure the average particle size of metal composite hydroxide, and measure d10 and d90, calculate the index of the width of particle size distribution, namely (d90-d10) / average particle size). As a result, it is confirmed that the average particle size of metal composite hydroxide is 5.4 μm, and (d90-d10) / average particle size) is 0.43.

[0283] In addition, in order to confirm whether there is a tungsten concentration layer in the metal composite hydroxide and its thickness, an energy dispersive X-ray analyzer (EDX) mounted on a scanning transmission electron microscope (manufactured by Hitachi High-Technologies Corporation, HD-2300A) was used to perform surface analysis of the cross section of the metal composite hydroxide. As a result, it was confirmed that a portion (tungsten concentration layer) where tungsten exists in a concentrated manner in the surface layer of the metal composite hydroxide was formed, and its thickness (the average range of the thickness of each secondary particle analyzed) was confirmed to be 3 to 8 nm.

[0284] In addition, the tap density is to use a vibration specific gravity measuring device (manufactured by Co., Ltd., KRS-409) to fill the obtained metal composite hydroxide into a 20 ml graduated cylinder, and then the graduated cylinder is repeatedly dropped from a height of 2 cm 500 times to make it tightly filled and measured. The composition and evaluation results of the above-mentioned manufacturing conditions, the obtained metal composite hydroxide are shown in Table 1.

[0285] (c) Preparation of positive electrode active material

[0286] Using a vibrating mixing device (TURBULA Type T2C manufactured by WAB), the metal composite hydroxide obtained as above is fully mixed with lithium carbonate in a manner of Li / Me of 1.14 to obtain a lithium mixture. The lithium mixture is heated to 950°C at a heating rate of 2.5°C / min in an air flow of air (oxygen concentration: 21% by volume), kept at this temperature for 4 hours and roasted, and cooled to room temperature at a cooling rate of about 4°C / min. The positive electrode active material thus obtained is aggregated or slightly sintered. Therefore, the positive electrode active material is crushed to adjust the average particle size and particle size distribution.

[0287] (d) Evaluation of positive electrode active material

[0288] The positive electrode active material was confirmed to be composed of the general formula: Li 1.14 Ni 0.38 Mn 0.30 Co 0.32 Zr 0.002 W 0.005 O2 represents the substance. In addition, the average particle size of the lithium metal composite oxide was measured using a laser diffraction scattering particle size analyzer, and d10 and d90 were measured to calculate the index representing the width of the particle size distribution, namely [(d90-d10) / average particle size]. As a result, it was confirmed that the average particle size of the lithium metal composite oxide was 5.3 μm, [(d90-d10) / average particle size] was 0.43, and the d50 ratio was 1.04.

[0289] In addition, the crystallite diameter of the (003) plane was measured using an X-ray diffraction apparatus (manufactured by Spectris Corporation, X'Pert PRO). The result was (144.6nm).

[0290] In addition, in order to confirm the distribution of tungsten in the lithium metal composite oxide using a scanning transmission electron microscope, a surface analysis of the cross section of the lithium metal composite oxide was performed using an energy dispersive X-ray analyzer (EDX). As a result, it was confirmed that in the lithium metal composite oxide, a large amount of tungsten was contained in the surface layer of the primary particles near the surface of the secondary particles and in the grain boundaries between the primary particles.

[0291] In addition, the tap density was evaluated under the same conditions as those for the metal composite hydroxide.

[0292] (e) Fabrication of secondary batteries

[0293] Figure 7 This is a diagram showing a 2032-type button cell CBA used in the evaluation of battery characteristics. Figure 7 A method for producing a secondary battery will be described.

[0294] 52.5 mg of the positive electrode active material obtained as above, 15 mg of acetylene black and 7.5 mg of PTFE were mixed, pressed at a pressure of 100 MPa into a shape of 11 mm in diameter and 100 μm in thickness, and then dried in a vacuum dryer at 120° C. for 12 hours to prepare a positive electrode PE.

[0295] Next, using the positive electrode PE, a 2032-type button battery CBA was made in a glove box with an Ar atmosphere whose dew point was managed at -80°C. The negative electrode NE of the 2032-type button battery CBA uses lithium metal with a diameter of 17 mm and a thickness of 1 mm, and the electrolyte uses an equal mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) with 1M LiClO4 as the supporting electrolyte (manufactured by Toyama Pharmaceutical Industry Co., Ltd.). In addition, the separator SE uses a polyethylene porous membrane with a film thickness of 25 μm. It should be noted that the 2032-type button battery CBA has a gasket GA, which is assembled into a button-shaped battery by the positive electrode tank PC and the negative electrode tank NC.

[0296] (f) Battery evaluation

[0297] [resistance]

[0298] The resistance value of the button cell CBA assembled above was measured by the AC impedance method at SOC 20%, and the relative value with respect to the resistance value of Ref. was calculated based on Comparative Example 1, and the result was 92.9%. The evaluation results are shown in Table 2.

[0299] (Examples 2 to 8)

[0300] As shown in Table 1, metal composite hydroxides were obtained under the same conditions as in Example 1 except that the timing (addition time) of adding the tungsten-containing aqueous solution during particle growth was changed. The evaluation results of the obtained metal composite hydroxides are shown in Table 1, and the evaluation results of the obtained positive electrode active materials are shown in Table 2.

[0301] Figure 8(A) shows the distribution of W obtained by surface analysis of the cross section of the metal composite hydroxide obtained in Example 4 using an energy dispersive X-ray analyzer (EDX) mounted on a scanning transmission electron microscope (manufactured by Hitachi High-Technologies Corporation, HD-2300A). As a result, for the metal composite hydroxide obtained in Example 4, as with the metal composite hydroxides obtained in other examples, a portion (tungsten concentration layer) where tungsten is concentrated on the surface of the secondary particles was detected, and its thickness was confirmed to be 40nm to 45nm. In addition, Fig. 9 FIG. 1 is a diagram showing an example of a SEM image when a cross section of a metal composite hydroxide obtained in an example is observed by a scanning electron microscope (SEM). Fig. 9 As shown, it was confirmed that the metal composite hydroxide obtained in the example had a hollow structure.

[0302] Next, a cathode active material and a secondary battery were obtained under the same conditions as in Example 1 except that the obtained metal composite hydroxide was used as a precursor. Table 1 shows the evaluation results of the obtained metal composite hydroxide and cathode active material.

[0303] Fig.10 The distribution of W obtained by surface analysis of the cross section of the lithium metal composite oxide obtained in Example 4 using an energy dispersive X-ray analyzer (EDX) mounted on a scanning transmission electron microscope (manufactured by Hitachi High-Technologies Corporation, HD-2300A) is shown. As a result, for the lithium metal composite oxide obtained in Example 4, similarly to the lithium metal composite oxides obtained in other Examples, it was confirmed that tungsten was present in large quantities in the surface layer of the primary particles near the surface of the secondary particles and in the grain boundaries between the primary particles.

[0304] (Comparative Example 1)

[0305] A metal composite hydroxide was obtained under the same conditions as in Example 1 except that a tungsten compound was added (addition range was 100%) from the start of the particle growth step. The evaluation results of the obtained metal composite hydroxide are shown in Table 1. Next, a positive electrode active material and a secondary battery were prepared under the same conditions as in Example 1 except that the obtained metal composite hydroxide was used as a precursor. The evaluation results of the obtained positive electrode active material and the secondary battery are shown in Tables 1 and 2.

[0306] (Comparative Example 2)

[0307] In addition to using metal composite hydroxides (Ni 0.38 Mn 0.30 Co 0.32 Zr 0.002A positive electrode active material (Li) was prepared under the same conditions as in Example 1, except that tungsten oxide was added to the mixture of metal composite hydroxide and lithium carbonate to obtain a lithium mixture (external addition). 1.14 Ni 0.38 Mn 0.30 Co 0.32 Zr 0.002 W 0.005 The evaluation results of the obtained positive electrode active material and the secondary battery are shown in Tables 1 and 2.

[0308] (Comparative Example 3)

[0309] A metal composite hydroxide, a positive electrode active material and a secondary battery were prepared under the same conditions as in Example 1, except that the sodium tungstate aqueous solution was not supplied in the second crystallization step during the crystallization step. The evaluation results of the obtained metal composite hydroxide, positive electrode active material and secondary battery are shown in Tables 1 and 2.

[0310] [Table 1]

[0311]

[0312] [Table 2]

[0313]

[0314] (Evaluation results)

[0315] The metal composite hydroxide obtained in the embodiment was confirmed to have a tungsten concentration layer formed on its surface. In addition, compared with Comparative Example 1 in which tungsten was added throughout the crystallization process, the positive electrode active material obtained in the embodiment had a larger crystallite diameter and showed a low resistance value when used as the positive electrode of a secondary battery.

[0316] In addition, the metal composite hydroxides obtained in Examples 1 to 6 form a tungsten concentration layer with a thickness of less than 100 nm. The positive electrode active material obtained using these metal composite hydroxides as precursors has a larger crystallite diameter than that of Comparative Example 2 in which a tungsten compound is added, and shows a lower resistance value when used as a positive electrode of a secondary battery.

[0317] On the other hand, the positive electrode active material obtained in Comparative Example 3 without tungsten addition had a larger crystallite diameter than other Examples and Comparative Examples in which tungsten was added, but showed a large resistance value and poor output characteristics when used as a positive electrode of a secondary battery.

[0318] The embodiments of the present invention are described above, but the technical scope of the present invention is not limited to the methods described in the above embodiments, etc. Sometimes one or more of the features described in the above embodiments, etc. may be omitted. In addition, the features described in the above embodiments, etc. may be appropriately combined. In addition, the contents of Japanese Patent Application No. 2017-136324 and Japanese Patent Application No. 2018-041799, which are Japanese patent applications, and all the documents cited in this specification are cited as part of the description herein within the scope permitted by law.

[0319] Description of Reference Numerals

[0320] 10…Metal composite hydroxide

[0321] 1…Primary particles (metal composite hydroxide)

[0322] 2…Secondary particles (metal composite hydroxide)

[0323] 3…Tungsten Concentration Layer

[0324] 20…Lithium metal composite oxide

[0325] 21…Primary particles (lithium metal composite oxide)

[0326] 22…Secondary particles (lithium metal composite oxide)

[0327] 23…Compounds containing tungsten and lithium

[0328] 24…Gap

[0329] 25…Hollow part

[0330] 26…Space Department

[0331] CBA...Button battery

[0332] CA... Shell

[0333] PC... positive electrode tank

[0334] NC……Negative electrode tank

[0335] GA... Gasket

[0336] PE……positive electrode

[0337] NE... Negative electrode

[0338] SE...Separator

Claims

1. A metal composite hydroxide comprising nickel, manganese and tungsten and optionally cobalt and element M, wherein the atomic ratio of each metal element is represented by Ni:Mn:Co:W:M=x:y:z:a:b, wherein: x+y+z=1, 0.3≤x≤0.95, 0.05≤y≤0.55, 0≤z≤0.4, 0<a≤0.1, 0≤b≤0.1, M is one or more elements selected from Mg, Ca, Al, Ti, V, Cr, Zr, Nb, Mo, Hf and Ta, The metal composite hydroxide has a tungsten concentrated layer having a thickness of 200 nm or less in a direction from a surface of the metal composite hydroxide toward a center portion.

2. The metal composite hydroxide according to claim 1, wherein The thickness of the tungsten concentrated layer is less than 100 nm.

3. The metal composite hydroxide according to claim 1 or claim 2, wherein The metal composite hydroxide has an average particle size of 4.0 μm or more and 9.0 μm or less, and (d90-d10) / average particle size, which is an index indicating the width of particle size distribution, is 0.65 or less.

4. A positive electrode active material for a non-aqueous electrolyte secondary battery, comprising a lithium metal composite oxide, wherein the lithium metal composite oxide comprises lithium, nickel, manganese and tungsten and optionally cobalt and an element M, wherein the atomic ratio of each metal element is represented by Li:Ni:Co:Mn:W:M=1+u:x:y:z:a:b, wherein: x+y+z=1, -0.05≤u≤0.50, 0.3≤x≤0.95, 0.05≤y≤0.55, 0≤z≤0.4, 0<a≤0.1, 0≤b≤0.1, M is one or more elements selected from Mg, Ca, Al, Ti, V, Cr, Zr, Nb, Mo, Hf and Ta, The lithium metal composite oxide is obtained by using the metal composite oxide according to claim 1, The lithium metal composite oxide includes secondary particles formed by agglomeration of a plurality of primary particles, and a compound containing tungsten and lithium is concentratedly present on the surface of the secondary particles or in the surface layer of the primary particles present inside the secondary particles and in the grain boundaries between the primary particles.

5. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 4, wherein The lithium metal composite oxide has a tap density of 1.2 g / cm 3 Above 1.99g / cm 3 The following hollow structure.

6. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 4, wherein The crystallite diameter of the (003) plane measured by powder X-ray diffraction was 120 nm or more.

7. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, a separator and a non-aqueous electrolyte, wherein the positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 4 is used as a positive electrode material of the positive electrode.

Citation Information

Patent Citations

  • Lithium transition metal compound powder, its production method, spray dried product being baking precursor of the powder, positive electrode for lithium secondary battery using the product, and lithium secondary battery

    JP2008305777A

  • Lithium ion secondary battery

    JP2012079608A

  • Manganese composite hydroxide particle, positive pole active material for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery, and method for producing them

    JP2012246199A

  • Transition metal complex hydroxide suitable for precursor of positive electrode active material for nonaqueous electrolyte secondary battery and method for manufacturing the same, positive electrode active material for nonaqueous electrolyte secondary battery and method for manufacturing the same, and nonaqueous electrolyte secondary battery comprising the positive electrode active material

    JP2012252844A

  • Positive electrode active material for nonaqueous electrolyte secondary battery, method for manufacturing the same, and nonaqueous electrolyte secondary battery including the positive electrode active material

    JP2013125732A